Effects of open cell foam support on Ni-based catalysts for low concentration methane oxidation - Shengtai Yan; Kairui Shen; Xinjiang Dong; Yifan Ding; Li Yang; Fang Liu (Fuel, 2026)

Spermatogenic arrest of cattle-yak originated from aberrational transition from gonocytes to spermatogonia and aggravated at pachytene primary spermatocyte stage - Peng Zhang; Zhenhua Shen; Wenjing Dong; Shujun Guo; TserangDonko Mipam; Xianrong Xiong; Jian Li; Xin Cai (Theriogenology, 2026)

Dynamic evolution characteristics of coal reactivity under burnt metamorphism during underground coal gasification - Maifan Dong; Botao Qin; Lele Feng; Jie Dong; Haidong Li; Saeideh Babaee; Huaizhan Li; Jian Shen (Fuel, 2026)

Modeling maize yield response to evapotranspiration via net primary productivity: A spatially explicit framework for a major corn-belt region - Qichen Zhang; Weihong Dong; Xiaosi Su; Tiejun Song; Xiaofang Shen; Li Lu (Field Crops Research, 2026)

A facile and scalable strategy to construct superhydrophilic PET membranes for ultrahigh-flux oil–water separation - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2026)

Valorizing lignocellulosic biomass-derived hydrothermal carbonization aqueous phase for heavy metal removal from contaminated soil: Molecular composition-mediated metal-specific complexation - Mei Huang; Yangchun Li; Yangziyun Zhang; Zhi Liao; Li Zhao; Dong Tian; Yan Liu; Yongjia Lei; Yu Zhao; Shuanglin Chen; Fei Shen (Bioresource Technology, 2026)

Catalytic conversion of glucose to furfural via asymmetrical C-C bond scission: Insight into the location and configuration of framework Sn species - Weijie Shen; Li Dong; Shuoqi Pei; Guoqiang Ding; Shanhui Zhu; Yueqing Wang; Guangping Lei; Yulei Zhu (Biomass and Bioenergy, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Expression patterns and proliferative effect of OTUD6A on Sertoli cells and Leydig cells in cattleyak - Wenjing Dong; Peng Zhang; Zhenhua Shen; Shujun Guo; TserangDonko Mipam; Xianrong Xiong; Jian Li; Xin Cai (Theriogenology, 2026)

Mechanical disturbance of trichomes enhances Cd2+ accumulation via malate-mediated stomatal opening in Arabidopsis - Juan Du; Hongyang Wei; Tongxin Shen; Xue Chang; Mingyu Hao; Yang Qi; Ning Liu; Zhiyan Cao; Jingao Dong; Li Hong Zhou (Plant Science, 2026)

A review of the application of machine learning in the field of fire public safety: From risk assessment to emergency decision-making - Xin Dong; Jiayue Zhou; Jun Shen; Chiyuan Li; Tianwei Zhang; Sicheng Fan; Qianqian Song (Energy and Buildings, 2026)

Polymerized chlorquinaldol-integrated fibrous membrane as a dual-functional barrier for anti-adhesion therapy - Qing Yu; Weijun Huang; Xinpeng Dong; Xuefeng Jiang; Shen Liu; Yusheng Li (Chemical Engineering Journal, 2026)

Distinct testicular somatic cell profiles in cattle-yak with spermatogenic arrest compared to yak - Peng Zhang; Zhenhua Shen; Shixin Wu; Wenjing Dong; Shujun Guo; Qiuyun Li; Xinrui Wu; Hongliang Chen; TserangDonko Mipam; Xianrong Xiong; Jian Li; Xin Cai (Theriogenology, 2026)

Corrigendum to “Collaboratively optimize of multi-scale spatial form within urban blocks for low-carbon performance: A machine learning-driven design support framework” [Sustainable Cities and Society, 143 (2026), 107342] - Gaomei Li; Hongxin Guo; Jian Kang; Yichen Dong; Hua Zhong; Anting Gao; Wei Lu; Shen Xu (Sustainable Cities and Society, 2026)

Exogenous microbial metabolites improve rhizosphere microecology and reduce Fusarium abundance to control root rot in wolfberry - Dong Zhao; Tingting Xu; Hongyu Chen; Shuo Shen; Shuqun Deng; Junlong Feng; Chenxu Gao; Jiali Ning; Zhuofei Zhang; Zhongyang Xu; Wei Li; Yang Zhang (Rhizosphere, 2026)

Paleozoic metamorphism and deformation process of the North Qinling Terrane: Implications for the closure of the northernmost Proto-Tethys Ocean - Yining Zhang; Shengsi Sun; Yunpeng Dong; Junsheng Lu; Xinyu Li; Chunqiang Shen; Yixi Li (Lithos, 2026)

Continental crustal growth in collisional orogens: Insights from the Triassic granitoids in East Kunlun, NW China - Wen-Jia Wang; Xiao-Wei Li; Yang-Ming Hu; Yong Zhang; Shuang Dai; Da-Ming Zhang; Dong-Bao Guo; Chang-Hai Luo; Juan Shen; Cheng-Yong Wang; Wei-Ming Ma (Lithos, 2026)

Synergistic micro-nano bubble treatment via high-speed vortex and ultrasound enhances quality and safety of lettuce and cherry tomatoes - Xiaolan Li; Yan Dong; Jiangning Shen; Lingzhi Zhang; Xianli Gao; Bo Wang; Zhi-Hong Zhang (Food Research International, 2026)

Antibacterial liquid tympanic membrane bandage for perforation repair and instant hearing restoration - Yiming Ma; Jiabei Luo; Shiyuan Li; Yuefan Jin; Jiayu Li; Jingjing Cai; Yingying Zhang; Yueyi Shang; Wenxin Shen; Hongyu Dong; Shankai Yin; Chengyi Hou; et al. (Chemical Engineering Journal, 2026)

Ultrasound-activated endoplasmic reticulum-targeting piezoelectric nanoagonist with auxiliary intrinsic efficacy reverses tumor immunosuppression via spatiotemporal ICD in ovarian cancer - Shuangshuang Cheng; Haojia Li; Yuwei Yao; Ting Zhou; Wan Shu; Jiarui Zhang; Tangansu Zhang; Guanglei Zhong; Guanxiao Chen; Xiaoyu Shen; Yingying Peng; Shuyang Yu; et al. (Chemical Engineering Journal, 2026)

MT2A facilitates the malignant progression of clear cell renal cell carcinoma by activating the TFAP2A/YAP axis via histone lactylation - Weiping Huang; Feng Jiang; Weizhi Zhang; Yiting Dong; Mengyuan Li; Mengting Shen; Dalin He; Jianjian Zheng; Zhixian Yu (Chemico-Biological Interactions, 2026)

Corrigendum to “Multiplex engineering of Candida tropicalis for efficient production of astaxanthin” [Bioresour. Technol. 454 (2026) 134718] - Xiaoying Gui; Jiaxuan Ji; Shuxian Hu; Xiyun Zhang; Yufeng Dong; Chenyang Wu; Yuanyuan Xia; Haiquan Yang; Wei Shen; Yu Cao; Li Zhou; Xianzhong Chen (Bioresource Technology, 2026)

Land-Use Type Dominates Over Rhizosphere Effects on phoC- and phoD-Harboring Bacterial Communities in Acidic Soils - Xiaoli Li; Xun Xiao; Long Guo; Xiao Ying Dong; Ren Fang Shen; Xue Qiang Zhao (Journal of Soil Science and Plant Nutrition, 2026)

Annual Variation of Secondary Organic Aerosols from Isoprene, α/β-Pinene, β-Caryophyllene, and Aromatics in Tropical Rainforest Area of Southwest China - Xiao Guo; Yali Liu; Minxia Shen; Weining Qi; Yifan Zhang; Lu Li; Yue Cao; Yingkun Jiang; Qian Wang; Shicong Li; Zhuoer Dong; Wenting Dai; et al. (Aerosol Science and Engineering, 2026)

A rapid optimization framework for high-rise office block design elements driven by carbon emission performance: Perspectives from three climate zones in China - Shen Xu; Qiuguo He; Tao Luo; Yichen Dong; Hua Zhong; Junchao Duan; Gaomei Li (Sustainable Cities and Society, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

The maize CMS-C fertility restore gene ZmRf4b encodes a SPL transcription factor that represses ZmMAP1D-mediated co-translational turnover of mitochondrial toxic ATP6C protein - Bing Li; Huaisheng Zhang; Runbo Zhang; Shicheng Feng; Fanli Yang; Congnian Ding; Xuyuan Shen; Keke Shao; Lu Yang; Yanan Lin; Dong Ding; Quancan Hou; et al. (Molecular Plant, 2026)

Evaluation of a full-scale two-stage anoxic/oxic–ultrafiltration–reverse osmosis process for landfill leachate treatment: Performance and microbial community succession - Erming Luo; Jia Ouyang; Xiaoqin Li; Honggang Chen; Zhongjie Lei; Min Shen; Xinxin Zhang; Qian Lu; Dong Wei; Chunying Li; Li Wei (Journal of Water Process Engineering, 2026)

Manganese-based heterogeneous advanced oxidation catalysts for the treatment of penetrant inspection wastewater - Yaohua Dong; Yuanyuan Shen; Dongyang Wu; Lanxin Yan; Weihang Jiang; Guodong Li (Journal of Water Process Engineering, 2026)

Quantitative study on multiphase flow displacement processes of water-LNAPL-gas influenced by groundwater table fluctuations - Zhijiang Yuan; Xiaosi Su; Chao Wang; Hang Lyu; Weihong Dong; Xiaofang Shen; Ningfei Li; Haiting Liang; Yazhi Song (Journal of Hydrology, 2026)

Irrigation enhanced nitrification and hydrological partitioning drive groundwater nitrate accumulation in an agricultural irrigation district - Xu Yang; Ruihong Yu; Guanglei Yu; Yansong Bai; Shen Qu; Dong Qian; Muhan Li; Zeyuan Liu; Ping Miao; Hongli Ma (Journal of Hydrology, 2026)

Enhancing anammox start-up for moderate- to low-strength ammonium wastewater: Adaptation of mature anammox sludge to high- and low-loading strategies - Yuerong Ding; Qian Zhang; Xiaoqian Dong; Bin Zhang; Yong Huang; Daosen Wu; Haonan Shen; Zhiyao Huang; Meng Li; Hongyu Wang (Environmental Research, 2026)

Shaking table test of a long-period three-dimensional base-isolated steel frame structure with flexible vertical guiding devices - Yundong Shi; Qi Wang; Yuchen Wang; Xuan Wang; Hongyi Shen; Wenqing Dong; Zhong-Xian Li (Engineering Structures, 2026)

Corrigendum to “Efficient production of nisin and diverse lanthipeptides in Escherichia coli through coordination of expression, modification, and maturation in a tailormade compartmentalized biosynthetic platform” [Chemical Engineering Journal 535 (2026) 175479] - Feiya Suo; Huihui Zhu; Yu Shen; Zijie Li; Linpei Zhang; Shijie Ma; Guangpeng Dong; Wenjing Cui; Zhemin Zhou (Chemical Engineering Journal, 2026)

Injectable adhesive hydrogel with self-assembled dual-enzyme nanofibers for spatiotemporal modulation of inflammation and axon regeneration after spinal cord injury - Qi Sha; Yuan Li; Zuomeng Wu; Yankai Wang; Yunxiao Fang; Ao Liu; Shunfeng Liu; Yixiang Dong; Lu Ye; Yue Qin; Shuhui Sun; Junjie Zhao; et al. (Chemical Engineering Journal, 2026)

Multiplex engineering of Candida tropicalis for efficient production of astaxanthin - Xiaoying Gui; Jiaxuan Ji; Shuxian Hu; Xiyun Zhang; Yufeng Dong; Chenyang Wu; Yuanyuan Xia; Haiquan Yang; Wei Shen; Yu Cao; Li Zhou; Xianzhong Chen (Bioresource Technology, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

Dietary betaine enhances muscle quality in largemouth bass: Insights into texture property, nutrient deposition, and lipid metabolic regulation under high-fat feeding - Xiaojing Dong; Fangxi Li; Mengjie Zhao; Jianqiao Wang; Xueyan Shen; Guangyang Zhang; Ao Li; Yuanyuan Fu; Hongying Fan; Anran Wang; Shuyan Miao; Xuedi Du (Aquaculture, 2026)

Spatiotemporal and Structural Differences of Two Types of MCSs and Their Circulation Environments Before and After Monsoon Onset Over South China - Yuqing Ruan; Rudi Xia; Xinghua Bao; Hongyan Wang; Mingxin Li; Yan Shen; Dong Zheng (International Journal of Climatology, 2026)
This study investigates the spatiotemporal characteristics, structural features and environmental conditions of mesoscale convective systems (MCSs) over the coastal region of South China from April to June during 2013–2017, using satellite–gauge merged precipitation, cloud‐to‐ground (CG) lightning data, radar observations and reanalysis data. All analysed MCSs generate rainfall and are classified into two categories based on lightning activity: rainfall‐only MCSs (without observed CG lightning) and lightning‐producing MCSs (rainfall with CG lightning). Their spatial structures, rainfall and lightning behaviours and associated circulation patterns are compared, with emphasis on variations before and after monsoon onset. Results show that lightning‐producing MCSs are generally larger in both horizontal and vertical extent than rainfall‐only MCSs, especially after monsoon onset, when both types become more vertically developed. Before monsoon onset, lightning‐producing MCSs are less frequent but produce stronger rainfall. After monsoon onset, their frequency increases while rainfall intensity weakens. In contrast, rainfall‐only MCSs show increases in both frequency and rainfall intensity after monsoon onset. The formation of lightning hotspots is influenced by both the frequency of lightning‐producing MCS occurrences and their internal lightning intensity, with the latter playing a more dominant role. Circulation types favourable for MCS development differ significantly. Lightning‐producing MCSs tend to occur along the western flank of the subtropical high under southwesterly low‐level winds, with convective instability peaking in the afternoon. Rainfall‐only MCSs are more common within the subtropical high under southeasterly flows, where nocturnal convergence and orographic lifting promote their development. These circulation differences are shaped by seasonal variations in moisture, thermodynamics and topography. This study provides a comprehensive understanding of MCS‐related rainfall and lightning, offering insights for forecasting and model evaluation.

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Species-specific environmental niches govern biogeographic patterns and seasonal dynamics of the harmful algal genus Phaeocystis in Chinese seas - Pingping Shen; Jiayi Shi; Xuejun Fu; Qingshang Song; Yue Xue; Xiyan Wang; Mengqi Dong; Haiping Li (Environmental Pollution, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Monitoring the thermal characteristics of surrounding permafrost during bridge operation in unstable and high ice content permafrost site of the Qinghai-Tibet Plateau - Xin Hou; Ji Chen; Jiawei Gao; Yuerong Li; Shouhong Zhang; Tianchun Dong; Yaojun Zhao; Shen Ma (Cold Regions Science and Technology, 2026)

Polyethylene glycol–liposomal doxorubicin triggers ferroptosis in breast cancer through the KEAP1/NRF2 signaling pathway - Yuanyuan Shen; Qingling Hua; Jinnan Wang; Menghao Dong; Wencheng Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Groundwater-surface water interactions and material fluxes in a typical watershed, Ordos Plateau, NW China: insight from hydrochemistry, stable isotopes and 222Rn mass balance model - Wei Bao; Yixuan Wang; Ao Gao; Jiping Yao; Shen Qu; Jiajun Li; Dong Qian; Le Qiao; Lijuan Hu; Hongli Ma; Ping Miao; Haixia Wu; et al. (Environmental Geochemistry and Health, 2026)

A native Trichoderma brevicompactum enhances nutrient acquisition and growth of Malus hupehensis in calcareous soil: evidence for microbiome context dependence - Hao Li; Hongwei Gai; Xiao Hu; Yanwei Ma; Qincong Wu; Lijun Huang; Yuzhuo Meng; Feixue He; Yangchun Xu; Caixia Dong; Qirong Shen (Applied Soil Ecology, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Spray Dried Lysozyme Microspheres: Morphological Evolution and Enzymatic Activity Retention - Mengyuan Li; Shen Yan; Shengyu Zhang; Xiao Dong Chen; Winston Duo Wu (Pharmaceutical Research, 2026)

Structural and dynamic insights into SPDT for phosphorus allocation in rice - Haitao He; Yan Liu; Jie Zhang; Xiaofeng Zheng; Lihuan Jiang; Zhangmeng Du; Jiaqi Zuo; Shuo Cao; Xuemei Peng; Zhiwen Zheng; Kun Li; Cuicui Shen; et al. (Science China Life Sciences, 2026)

Multiscale quantification of LNAPL redistribution processes in multiphase systems under groundwater table fluctuation influences - Zhijiang Yuan; Xiaosi Su; Hang Lyu; Chao Wang; Ningfei Li; Haiting Liang; Yazhi Song; Xiaofang Shen; Weihong Dong; Tiejun Song; Wen Yao (Water Research, 2026)

Collaboratively optimize of multi-scale spatial form within urban blocks for low-carbon performance: A machine learning-driven design support framework - Gaomei Li; Hongxin Guo; Jian Kang; Yichen Dong; Hua Zhong; Anting Gao; Wei Lu; Shen Xu (Sustainable Cities and Society, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Efficient persulfate activation via a novel layered porous biochar enhanced with nano-zero-valent iron loading and synergistic sulfidation modification: Performance and mechanism - Lei Shen; Zichen Qin; Yuanding Shi; Yan Li; Pengyao Guo; Jinwei Zhang; Yijun Shen; Chun Yang; Yuchen Zeng; Dongxiao Sun; Zhiqiang Dong; Lei Ding (Journal of Water Process Engineering, 2026)

Optimized hot-air drying enhances gastrodin content and antioxidant activity in Gastrodia elata: insights from chemical and microstructural analyses - Jianduo Shen; Long Zhang; Qingxing Dong; Yuqian Jiang; Xuejin Li; Mengru Li; Rameesha Anjum; Wenju Ji; Shiming Li; Xiaoying Zhang; Yao Tang (Food Chemistry, 2026)

The synergistic effects of multiple urban morphological factors on building and residential travel carbon emissions at the neighborhood scale - Yuchen Qin; Yuchen Xie; Yichen Dong; Qi Zhang; Xiaoping Li; Qiwei Chen; Minghao Wang; Shen Xu (Energy and Buildings, 2026)

An Optimization Framework for Pressure Monitoring in Water Distribution Networks: Coupling Krill Herd Algorithm with Monte Carlo-Based Uncertainty Analysis - Peng Feng; Shen Dong; Hang Li; Mou Lv (Water Resources Management, 2026)

A plant-free push–pull system using sustained-release electrospun micro-/nanofibers for insect behavioral manipulation - Chenglong Cui; Xiwei Xia; Zhimin Wang; Ertao Li; Huanhuan Dong; Jiaan Shen; Yujun Sun; Yu Peng; Kebin Li; Jiao Yin (Journal of Pest Science, 2026)

Distinct dose-response patterns between methane production and oxidation to urea or (NH4)2SO4 input in Chinese paddy fields - Wang-ting Yang; Bing-jie Ren; Si-le Wen; Yi-zhu Zhu; Jiang-bing Xu; Li-dong Shen; Wei-qi Wang; Jordi Sardans; Josep Peñuelas (Applied Soil Ecology, 2026)

Viral communities as mirrors and vectors: Tracing antibiotic resistome distribution and dissemination across diverse habitats in Macao - Yu-Qiu Ye; Da Lin; Luo-Qin Shen; Di Wu; Ying Li; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2026)

Molecular characteristics of organic aerosols and impacts of transboundary biomass burning in Southwest China - Zhuoer Dong; Yali Liu; Xiao Guo; Jiaying Yu; Minxia Shen; Weining Qi; Yifan Zhang; Lu Li; Yue Cao; Yingkun Jiang; Qian Wang; Shicong Li; et al. (Journal of Hazardous Materials, 2026)

Synergistically enhanced mechanical properties, wave-transparency, and low dielectric properties of cyanate ester resins by furfuryl-based diglycidyl-containing hollow polymer microspheres with nanoconfinement effects - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2026)

Efficient production of nisin and diverse lanthipeptides in Escherichia coli through coordination of expression, modification, and maturation in a tailormade compartmentalized biosynthetic platform - Feiya Suo; Huihui Zhu; Yu Shen; Zijie Li; Linpei Zhang; Shijie Ma; Guangpeng Dong; Wenjing Cui; Zhemin Zhou (Chemical Engineering Journal, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

Search-Information-Driven Collaborative Task Planning for Multi-UUV Systems - Peng Chang; Yintao Wang; Dong Li; Qingliang Shen; Zhengqing Han (Journal of Marine Science and Engineering, 2026)
To address the problems of unreasonable task allocation and low target search efficiency in the collaborative search of multiple unmanned undersea vehicles (UUVs) in complex marine environments, this paper proposes a search-information-driven collaborative task planning method for multi-UUV systems, and constructs a systematic and integrated multi-UUV collaborative task planning framework. Considering the spatial characteristics of the complex underwater environment and sonar detection rules, an underwater task environment grid model and an active sonar instantaneous detection model are constructed as the environmental and detection foundation of the framework. Within the framework, the Gaussian Mixture Model (GMM) is adopted to realize dynamic division of task regions, and reasonable resource allocation among multiple UUVs is achieved by defining scientific area allocation indicators. A search information map consisting of target probability distribution and environmental uncertainty is established, and a receding horizon planning framework is introduced to balance short-term detection effectiveness and long-term search value. Furthermore, a motion-coded Grey Wolf Optimization (GWO) algorithm is proposed to generate continuous UUV paths, which avoids path discontinuity caused by discrete grids and ensures the convergence efficiency of the algorithm. Simulation results verify that compared with traditional methods, the proposed method improves the total probability benefit by 19.87% and the number of discovered targets by 18.29%, demonstrating better search performance and environmental adaptability.

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Simultaneous removal of dissolved organic matter, nitrogen, and phosphorus from secondary effluent in a zero-valent iron (ZVI) assisted pyrite autotrophic denitrification biofilter - Siqi Liu; Zhen Shen; Mengqing Li; Yongfang Zhang; Xinwen Zhang; Dong Wei (Journal of Water Process Engineering, 2026)

Temporal dynamics of mercury exposure and associated health and economic burdens in China - Meilin Yan; Yixue Wu; Qingru Wu; Zhaomin Dong; Chenyue Niu; Xin Li; Xianbao Shen; Zhiliang Yao (Journal of Environmental Management, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Low-carbon renovation of old residential blocks: An envelope-focused assessment framework for carbon reduction effects and economic benefits - Shen Xu; Yichen Dong; Hongxin Guo; Zhen Yu; Bo Pan; Congyue Qi; Gaomei Li (Energy and Buildings, 2026)

Supersaturated salt hydrogels for humidity regulation in food preservation - Wanfeng Wu; Siyang Li; Hui Yuan; Yifeng Shen; Yaoting Xue; Nannan Dong; Yaoqi Zhang; Mengfei Mao; Zisheng Luo; Tiefeng Li; Li Li; Xuxu Yang (Chemical Engineering Journal, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Advantages of partial denitrification–anaerobic ammonium oxidation system under sulfamethoxazole stress: Adaptive mechanisms and synergistic metabolism - Jiantao Ji; Qiyue Wang; Feiyue Hu; Haosen Yang; Ying Li; Guanqi Wu; Yongen Dong; Jinying Du; Huiru Li; Bo Shen; Bo Wang (Bioresource Technology, 2026)

Integrated nanoarchitectonics of porous carbon with high specific surface area and liquid fertilizer from distiller's grains by hydrothermal process - Yao Zhao; Zhanglin Liu; Binglin Wang; Jinguang Hu; Mei Huang; Li Zhao; Dong Tian; Jinsong He; Jianmei Zou; Fei Shen (Biomass and Bioenergy, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Foot Progression Angle Modulates Knee Loading During Walking in Individuals with Flexible Flatfoot - Linxiao Shen; Zhenghui Lu; Xin Li; Zifan Xia; Yufan Xu; Chengyuan Zhu; Yang Song; Xuanzhen Cen; Dong Sun; Gusztáv Fekete; Yaodong Gu (Annals of Biomedical Engineering, 2026)

Quantifying the influencing factors on the spatiotemporal patterns of dune activity in the Tengger Desert, Northwestern China - Xuehua Che; Zhuolun Li; Shipei Dong; Jie Luo; Yingyibing Shen; Xue Peng (Geomorphology, 2026)

Automatic gully mapping using deep learning with boundary-stratified sampling and pixel balancing optimization: a case study of the Yuanjiang dry-hot valley - Jiajun Song; Yifan Dong; Li Shen; Wenyue Cao; Xiaoxi Zhou; Ronghua Zhong (CATENA, 2026)

Indigenous Trichoderma-based biofertilizer reshapes the pear rhizosphere microbiome for enhancing fruit quality under calcareous soil - Zuohereguli Kuerban; Rou jiang; Yanwei Ma; Sidong Li; Peigen Li; Liping Kan; Caixia Dong; Yangchun Xu; Qirong Shen (Plant and Soil, 2026)

Cropping Systems Mediate Carbon and Nitrogen Substrate Effects on Soil Carbon Dioxide and Nitrous Oxide Emissions - Yuan Li; Wenwen Liu; Ying Li; Tida Ge; Tongtong Guan; Dong-Gill Kim; Guopeng Liang; Narasinha Shurpali; Hem Raj Bhattarai; Perttu Virkajärvi; Kadambot H. M. Siddique; Yuying Shen (Journal of Soil Science and Plant Nutrition, 2026)
Agricultural management practices fundamentally influence soil greenhouse gas emissions, yet the mechanisms governing these emissions across different cropping systems remain incompletely understood. This study investigated how carbon (C) substrates and nitrogen (N) additions regulate carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) emissions in soils from contrasting agricultural systems. Using a factorial design, we examined the effects of C substrates (glucose, citric acid, glutamine) and N addition (KNO 3 ) on greenhouse gas emissions from soils under three-year continuous wheat ( Triticum aestivum ) or lucerne ( Medicago sativa ) cultivation. Lucerne soils showed consistently higher N 2 O emissions (0.42 ± 0.04 nmol m –2 s –1 ) compared to wheat soils (0.35 ± 0.03 nmol m –2 s –1 ). CO 2 emissions showed substrate-specific responses, with glutamine treatment yielding the highest emissions (1.35 ± 0.12 µmol m –2 s –1 ), followed by citric acid (1.12 ± 0.09 µmol m –2 s –1 ) and glucose (0.98 ± 0.08 µmol m –2 s –1 ), all significantly exceeding the water control (0.82 ± 0.07 µmol m –2 s –1 ). Structural equation modeling revealed that substrate effects were mediated through distinct pathways in each system, with iron availability and enzyme activities explaining 37% and 29% of emission variations in lucerne and wheat soils, respectively. Network analysis suggested strong correlations between N 2 O emissions and soil iron fractions ( r = 0.64–0.69) in both systems. Citric acid enhanced N 2 O emissions by 31% through pH-mediated effects on denitrification, while glucose and glutamine suppressed emissions by 24% and 18%, respectively, through enhanced N immobilization. The contrasting responses between systems reflected fundamental differences in microbial resource utilization strategies, with lucerne soils showing stronger coupling between C and N cycling processes (path coefficient = 0.45). These findings suggest that greenhouse gas mitigation strategies should consider both cropping system legacy effects and substrate-specific response patterns. System-specific approaches targeting both C input quality and N availability may offer effective pathways for emission reduction in agricultural soils.

Integrity and Performance Evaluation of Offshore Gravel-Pack Sand Control Completions in Unconsolidated Sandstone Reservoirs - Guolong Li; Changyin Dong; Chenfeng Liu; Kaixiang Shen; Tao Sun; Zhangyu Li (Journal of Marine Science and Engineering, 2026)
Unconsolidated sandstone reservoirs, particularly in offshore and marine environments, are highly susceptible to sand production, which leads to flow-capacity degradation, plugging evolution, sand-retention instability, and erosion–corrosion damage in gravel-pack completion systems. To address the lack of system-level and quantitative integrity evaluation methods, a unified assessment framework is developed by coupling flow behavior, sand-retention mechanisms, and erosion–corrosion damage processes. The gravel-pack completion system is idealized as a concentric multilayer porous-medium structure under steady-state radial Darcy flow, and an equivalent radial permeability model is established to characterize flow capacity and anti-plugging performance, which enables consistent comparison of different completion schemes under identical plugging conditions. Based on sand-retention mechanisms, a sand-retention capacity index is proposed by integrating formation particle size distribution, screen aperture, gravel size, and sand-leakage risk. An erosion–corrosion coupled damage model is further developed to predict screen damage rates in CO2-containing environments, and an integrity index is formulated to link damage evolution with long-term service performance. By integrating flow capacity, anti-plugging performance, sand-retention capacity, and structural integrity using a weighted geometric mean, a comprehensive evaluation index is established for overall system integrity assessment. Using the proposed framework, a representative formation sand with d10 = 30 μm, d50 = 180 μm, and d90 = 500 μm is evaluated. The optimal sand control design corresponds to a gravel median size of 971.53 μm (equivalent to a standard 16/20 mesh gravel) and an optimal screen aperture of 523.11 μm, with a screen porosity of 0.56. Under these conditions, the selected screen aperture and gravel size are well matched with the formation sand size, falling within recommended engineering ranges and achieving a favorable balance among sand retention, flow capacity, anti-plugging performance, and structural integrity. The proposed framework provides a quantitative and engineering-applicable basis for the optimization and integrity classification of offshore gravel-pack sand control completions under multi-constraint operating conditions.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Inhibitory effect of novel swirl flow injection technology on tar pollutant formation in underground coal gasification: Experiments and numerical simulation - Maifan Dong; Botao Qin; Lele Feng; Mingyue Weng; Huaizhan Li; Jian Shen (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “tumor microenvironment-responsive multifunctional nanoplatform with selective toxicity for MRI-guided photothermal/photodynamic/nitric oxide combined cancer therapy” [Chem. Eng. J. volume 481, 1 February 2024, 148618] - Shihao Zhou; Chengguang Wu; Pengfei Shen; Liming Zhou; Wenbo Wang; Kai Lv; Chengxiu Wei; Guowei Li; Dong Ma; Wei Xue (Chemical Engineering Journal, 2026)

Versatile fully polymeric conductive organohydrogel as an all-in-one wearable response platform for bioelectronics - Kelei Shi; Huiping Chen; Jianwei Li; Yupan Han; Hongling Sun; Hu Liu; Lin Dong; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2026)

Engineering desolvation-adsorption-catalytic interphases via in-situ copolymerization of polypyrrole and metal compounds for lithium sulfur batteries - Xinyi Gu; Zhoubin Yu; Weijian Li; Xinhui Xia; Jiayuan Xiang; Donghui Yang; Fangfang Tu; Yuanyuan Jiang; Tianqi Yang; Yi Dong; Ketong Chen; Yongfeng Yuan; et al. (Chemical Engineering Journal, 2026)

Livestock-induced changes in soil properties and microbial dominance determine soil microbial diversity in a conifer forest - Fan Fan; Jiangling Zhu; Kai Dong; Suhui Ma; Chengjun Ji; Zhiyao Tang; Shaopeng Wang; Xiaoli Shen; Sheng Li; Jingyun Fang (Soil Ecology Letters, 2026)

Ultra-low limit heparin detection based on 11-mercaptoundecanoic acid /chitosan functionalized and AuNPs enhanced fiber surface plasma - Jun Wu; Meijuan Jia; Meihui Zhang; Minglu Li; Shu Fang; Jie Dong; Anhua Dong; Ruotong Tian; Jun Zhou; Changyu Shen (Analytica Chimica Acta, 2026)

Low N Deposition Coupled With Climate Warming Promote Soil Asymbiotic N Fixation via Increasing Microbial Specialists in Alpine Grassland - Ke Zhang; Yaoming Li; Ran Zhang; Anna Du; Zuyan Ma; Hang Shi; Juejie Yang; Wenli Ding; Hao Shen; Richard D. Bardgett; Huaiying Yao; Shikui Dong (Global Change Biology, 2026)
Biological nitrogen fixation (BNF) is a vital process for introducing new N into natural ecosystems, and this process has been demonstrated to be suppressed by high N deposition. However, the net ecological effect and underlying mechanisms of BNF under chronic low‐level N deposition, characteristic of terrestrial ecosystems, remain highly uncertain. Given that climate warming is a key environmental change factor concurrent with N deposition, it is important to investigate whether climate warming can change BNF activity and alter the effects of N deposition on BNF. To fill these knowledge gaps, we implemented a decade‐long‐term manipulation experiment in an alpine grassland ecosystem with 5 treatments, that is, experimental warming (W), low‐level N deposition (N L ), high‐level N deposition (N H ), combination of climate warming and low‐level N deposition (WN L ) and the control (CK). BNF rate was measured by 15 N 2 isotope discrimination. We found that N L significantly stimulated BNF by 112%, contrasting sharply with the complete suppression under N H . Climate warming alone increased the BNF rate by 123%, while the WN L amplified this effect, stimulating BNF by 234%. Structural equation modeling revealed that WN L selectively favored specific diazotrophic groups ( Desulfovibrio ), whose proliferation directly drove the observed BNF shifts. In this N‐limited alpine grassland, low‐level chronic N deposition, especially when combined with warming, fundamentally shifts the diazotrophic community structure by driving a process of niche contraction. This selection process functionally enriches specialized diazotrophs, resulting in a dramatic, positive feedback that significantly promotes the overall biological nitrogen input. Our findings highlight the potential for increased N inputs under realistic future climate scenarios and provide a scientific basis for precision N management in alpine grasslands, both on the Qinghai‐Tibetan Plateau and worldwide.

Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

Genomic evidence reveals temperature-associated ecotypic divergence of Phaeocystis globosa in Chinese coastal waters - Mengqi Dong; Yue Xue; Haiping Li; Dayong Liang; Tao Yang; Yanying Zhang; Pingping Shen (Marine Pollution Bulletin, 2026)

Meridional tripole hydroclimate pattern changes in East Asian monsoon region of China during the Younger Dryas - Wenyu Dong; Wanyin Qiu; Kui Gao; Yue Li; Xing Liu; Yan Yang; Yi Wang; Xianfeng Wang; Chun-Yuan Huang; Chuan-Chou Shen; Binggui Cai; Xiuyang Jiang (Quaternary Science Reviews, 2026)

Acroeremophilanes A–I, eremophilane-type sesquiterpenoids from the Sinomenium acutum-derived symbiotic fungus Acrocalymma cycadis - Li-Bin Lin; Xue Cao; Wei Shi; Dan Shen; Mei-Niu Wang; Jing-Yu Wang; Jia-Hao Ning; Jia-Yao Hu; Dong-Zhu Duan; Xiao-Ling Wang; Jian Xiao (Phytochemistry, 2026)

Pinoresinol diglucoside alleviates hindlimb unloading-induced bone loss in mice - Ying-Ying Xuan; Liang Li; Yi Wu; Zhen-Long Wei; Mei Zhang; Min-Na Liu; Dong-Shuai Shen; Yu-Hai Gao; Cory J Xian; Hui-Ping Ma; Ke-Ming Chen (Life Sciences in Space Research, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Aptamer-driven upconversion fluorescence detection of dual pesticide residues in tea - Shuhua Li; Shen Zhang; Dong Li; Tianhui Jiao; Jie Wei; Xiaomei Chen; Qingmin Chen; Quansheng Chen (Food Chemistry, 2026)

Efficient electron transport in biomimetic porous nanospheres for photothermal-assisted catalytic hydrogen production - Aiyi Xie; Huixuan Xu; Qi Duan; Yanzong Zhang; Jinsong He; Li Zhao; Fei Shen; Dong Tian; Yan Liu (Chemical Engineering Journal, 2026)

Development of GLUT1-targeted/esterase-responsive brusatol prodrug liposomes for liver cancer therapy - Qiurong Liu; Yujue Wang; Jichong Li; Xiangyun Li; Zifang Ding; Yuge Li; Yanjiao Qiao; Tingyun Liu; Yaxu Wang; Yiwei Sun; Hao Zhou; Ziang Gao; et al. (Chemical Engineering Journal, 2026)

Novel senescence inducer ICA-11c, a derivative of icaritin, YAP-dependently suppresses hepatocellular carcinoma cells - Hong-fei Chen; Shuai Shen; Shuang-li Wang; Li Ye; Ji-chong Li; Wen-li Cao; Zi-lin Hou; Jian-huan Jia; Qing-bo Liu; Guo-dong Yao; Shao-jiang Song (Chemico-Biological Interactions, 2026)

Change of chemical compositions of the regional free troposphere in North China during COVID-19: Observational evidence from the Mt. Tai observatory - Yue Sun; Yujiao Zhu; Can Dong; Yingnan Zhang; Yujian Bi; Di Wu; Xiangkun Yin; Hengqing Shen; Tianshu Chen; Hongyong Li; Yuqiang Zhang; Qinyi Li; et al. (Atmospheric Environment, 2026)

RcLOG7-1 of castor bean plays dual roles in enhancing drought and salt stress tolerance - Yanxiao Li; Yang Shen; Wanhong Li; Yue Wang; Weifeng Dong; Mingzhe Sun; Dianjun Xiang; Xiaoli Sun; Peng Liu (Plant Cell Reports, 2026)

Long-term settlement prediction of shield tunnel interval considering spatial information - Dong-Mei Zhang; Zhao-Geng Chen; Yi-Ming Shen; Zhong-Kai Huang; Xiao-Chuang Xie; Xiao-Yang Guo; Deng-Fei Yan; Yong-Bo Li (Tunnelling and Underground Space Technology, 2025)

Longitudinal seismic response characteristics of shield tunnel structures in liquefiable soils - Yiyao Shen; M. Hesham El Naggar; Dong-Mei Zhang; Liyun Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2025)

Machine learning in ecotoxicology: Pollutant exposure levels and detection, biotoxicity and environmental behavior prediction - Xinyue Dong; Guanglei Zhao; Xi Chen; Mingrui Li; Chen Shen; Zhenguang Yan (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Gyroscopic effect-driven dynamics and incremental LQG tracking control for floating offshore wind turbines - Hao Wang; Jing-wei Zhou; Endi Zhai; Ji-hou Yang; Hao Tang; Qiang-song Li; Min-min Shen; Xiao-dong Yang (Ocean Engineering, 2025)

Straw-induced hematite-to-magnetite conversion in alkaline media: Experimental study and potential in Bayer process - Xin He; Guo-zhi Lv; Bing-shen Liu; Qing-dong Li; Xiao-lei Zhang; Zhuang-zhuang Yun; Ting-an Zhang (Minerals Engineering, 2025)

Spatio-temporal variability of lacustrine groundwater discharge and related pollutant fluxes in an agricultural drainage lake: Coupled influence of meteorological factors and vegetation coverage dynamics - Yuanzhen Zhao; Shen Qu; Muhan Li; Limin Duan; Yiming Zhao; Xiaohui Ren; Xu Yang; Shaogang Dong; Ruihong Yu (Journal of Hydrology, 2025)

Enhanced reduction behavior and efficient recovery of spent LiCoO2 oxygen carriers based on chemical looping principles - Jiyan Ma; Jiaojiao Liu; Kairui Shen; Jianing Shao; Xinjiang Dong; Lujin Li; Yifan Chen; Li Yang; Fang Liu (Journal of Environmental Chemical Engineering, 2025)

A computationally driven screening-construction-mechanism strategy of magnetic molecularly imprinted polymers for aliphatic aldehydes detection - Yongqing Zhang; Xiaolong Shang; Jiaqi Guo; Ling Ao; Caihong Shen; Miao Liu; Feng Lin; Wenxian Li; Liqiang Zhang; Baoguo Sun; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Highly sensitive and wide-range quantification of bovine αS1-casein in foods for predicting potential milk allergenicity using an IgE multi-epitope-specific antibody - Caiyi Shen; Liming Li; Caiyun Long; Yunbiao Luo; Yaping Dong; Jinyu Yu; Yi Yao; Guanrong Hu; Xin Li; Hongbing Chen; Shengfa He (Food Chemistry, 2025)

Comprehensive analysis and risk assessment of pyrethroid pesticide residues in the market-sold fruits from the Beijing-Tianjin-Hebei region, China - Jiangxue Dong; Qianwen Wu; Haoyun Yuan; Chenyu Ding; Zhaowei Fu; Zhuohan Liu; Hongyuan Yan; Xin Liu; Shigang Shen; Hui Li (Environmental Research, 2025)

One-step engineering of multifunctional ZIF-8/PES membrane for synergistic separation of selected proteins, dyes and antibiotics - Yanan Song; Rui Zhang; Baoyuan Dong; Yuan Liu; Mingming Zhang; Xiaoxue Hu; Jiake Li; Jianxian Zeng; Kaipeng Cheng; Lelin Zeng; Jie Shen (Desalination, 2025)

One polymer–multiple functions: Waterborne dual dynamic polyacrylate networks for self-healing and recyclable adhesives and coatings - Yu Chen; Wang Li; Rui Pu; Fengbiao Chen; Yujun Cheng; Yao Liu; Dong Luo; Siyu Nie; Xuelang Gao; Liang Shen; Fei Gao (Chemical Engineering Journal, 2025)

Phase-engineered Pt-MoS2 interaction with matched work function enables efficient hydrogen spillover for acidic hydrogen evolution - Yafei Cheng; Zhenyu Qiao; Mengmeng Xu; Huilong Dong; Yanlong Li; Junyu Shen; Hongbo Geng; Fan Liao; Zhenhui Kang (Chemical Engineering Journal, 2025)

Biomimetic stiffness modulator driven by bi-mode hydrogen bond locking mediated nano-heterogeneous aggregation - Chentong Gao; Xu Zhou; Yi Yang; Zhaoxu Yang; Xin Jing; Zemian Zuo; Jing Li; Binbin Dong; Hao-Yang Mi; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2025)

Low-temperature plasma mutagenesis breeding of Chlorella sorokiniana mutant strains for efficient carbon sequestration - Dong-Ao Li; Hong Zhang; Guang-Hui Xu; Jie Shen; Qing Huang (Bioresource Technology, 2025)

Gene expression of long non-coding RNAs and messenger RNAs in Varroa destructor mites exposed to essential oil of camphor leaves - Siyi Shen; Meng Li; Tongyu Dong; Kai Xu; Lili Wu; Kang Wang; Defang Niu; Qingsheng Niu; Ting Ji; Zhi Wang; Zheguang Lin (Experimental and Applied Acarology, 2025)

Detection of Caco-2 cell absorption rate of Bombyx mori peptide chelated zinc and validation of anti-inflammatory activity based on network pharmacology - Mengqing Guo; Ning Dong; Chunxue Liu; Rui Ma; Shen Li; Yao Sun; Fengqing Zhang (BioMetals, 2025)

Gastrodin Attenuates Neuroinflammation and Injury in Young Rats with LiCl/Pilocarpine-Induced Status Epilepticus - Jie Dai; Hai-lin Shen; Jia Li; Yong Zhou; Zheng-xie Dong; Xiang-yang Zhu (Biochemical Genetics, 2025)

Dose-response patterns of anaerobic oxidation of methane to nitrogen addition in Chinese paddy fields - Wang-ting Yang; Qi-nan Hu; Si-le Wen; Bing-jie Ren; Evgenios Agathokleous; Li-dong Shen; Wei-qi Wang (Soil Biology and Biochemistry, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

Micro-fluidic jet spray dried Pickering emulsion powders with high encapsulation efficiency: mechanistic insights into structural evolution during emulsion formation, drying and storage - Chaojie Wu; Shen Yan; Junhao Zhao; Mengyuan Li; Ziwei Nie; Shengyu Zhang; Xiao Dong Chen; Winston Duo Wu (Journal of Food Engineering, 2025)

Failure mechanism of rock tunnels subjected to combined reversed fault dislocation and subsequent seismic excitation - Dong-Mei Zhang; Li Guo; Zhong-Kai Huang; Yi-Yao Shen; Kyriazis Pitilakis (Computers and Geotechnics, 2025)

WITHDRAWN: Microbial diversity and cooperation in partial-denitrification/anammox system enhanced the synergistic metabolism of nitrogen and sulfamethoxazole - Jiantao Ji; Qiyue Wang; Feiyue Hu; Haosen Yang; Ying Li; Guanqi Wu; Yongen Dong; Jinying Du; Huiru Li; Bo Shen; Bo Wang (Chemical Engineering Journal, 2025)

Molecular design of non-fluorinated linear ethereal solvent for high-voltage Li metal batteries - Kaixin Ren; Tevin Li; Yun Shen; Guodong Li; Jinyu Yang; Shouyi Yuan; Xiaoli Dong; Fei Wang; Congxiao Wang; Junwei Lucas Bao; Yongyao Xia (Chemical Engineering Journal, 2025)

Pilot-scale non-sterile mixotrophic cultivation of Galdieria sulphuraria for high-efficient removal of ammonium with enhancing high-protein biomass production from industrial effluent - Yu Li; Dong Wei; Xiannan Peng; Hao Shen; Li Ni; Guoyou Wei (Bioresource Technology, 2025)

Optimizing hematite reduction in high - Iron bauxite during Bayer process via bagasse: A path to efficient resource utilization - Xin He; Guo-zhi Lv; Xiao-lei Zhang; Qing-dong Li; Bing-shen Liu; Zhuang-zhuang Yun; Ting-an Zhang (Biomass and Bioenergy, 2025)

SnRNA-seq Interprets Mechanisms by which Three Glial Cell Types Influence Myelin Regeneration in Adult Drug-Resistant Epilepsy-Related Cognitive Impairment - Lu Wang; Jia-Qi Ma; Yong-Qian Bian; Xiao-Peng Qu; Yue Zhang; Chao Wang; Guo-Dong Gao; Long-Long Zheng; Qi-Xing Fang; Li-Jia Song; Liang-Liang Shen; Bei Liu (Molecular Neurobiology, 2025)
Myelin regeneration has been shown in previous studies to ameliorate varying degrees of cognitive impairment in patients with neurodegenerative disorders such as epilepsy. The problem of myelin regeneration in adults with drug-resistant status epilepticus is a major key to the difficulty of treating cognitive impairment in adults with drug-resistant epilepsy (DRE). The purpose of this study is to provide a molecular map of myelin-related molecules under the cognitive deficits seen in DRE. We used a lamotrigine-pentylenetetrazol-resistant epilepsy mouse model and verified the cognitive problems and myelin changes using a water maze and conventional molecular biology techniques. We then analyzed the OLs in the hippocampus of the mice and the effect on myelin using sn RNA-seq technology. We found that the problem of cognitive impairment in drug-resistant epileptic mice is due to altered myelin plasticity. OL maturation induces pathological myelin regeneration which ultimately leads to cognitive impairment. The three glial cell types are closely related to the occurrence of myelin regeneration and jointly promote pathological myelin regeneration. Our study revealed the presence of myelin regeneration in DRE. All of this evidence suggests that normal myelin regeneration contributes to cognitive impairment improvement, but pathological myelin regeneration impairs cognition. Graphical Abstract Schematic representation of myelin regeneration in cognitive impairment in adult drug-resistant epilepsy. Boxed are pathways or molecules related to the promotion of myelin regeneration in which a subpopulation is involved. Red font indicates promotion, blue font indicates inhibition, and gray font indicates unknown but relevant.

Bio-organic fertilizer amendment helps suppress tomato bacterial wilt disease by improving aggregation and enhancing the pathogen inhibition capacity within micro-aggregates - Menghui Dong; Eiko E. Kuramae; Mengli Zhao; Yi Min; Shanshan Liu; Xu Xu; Qirong Shen; Rong Li; George A. Kowalchuk (Biology and Fertility of Soils, 2025)

Mechanistic insights into the quality maintenance of postharvest Cili induced by stress from exogenous H2O2 through ‘Physio-Omic-CompBio’ tripartite correlation - Jian Fan; Chunmei Li; Xiangli Wu; Yueyu Lu; Zhiwei Duan; Dong Cen; Ying Shen (Postharvest Biology and Technology, 2025)

UV-guided separation of polyacetylenol glycosides from the edible roots of Codonopsis pilosula and their anti-inflammatory activity - Xilan Jiang; Lun Wang; Yao Chen; Yi Zuo; Mengdan Liu; Bin Chen; Dong Fu; Yujiao He; Mingkui Wang; Ting Shen; Fu Li (Phytochemistry, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

Millennial-scale East Asian summer monsoon hydroclimate variability during 47–39 kyr B.P. inferred from a stalagmite IRMsoft-flux record in Southeastern China - Yue Li; Wanyin Qiu; Kui Gao; Wenyu Dong; Xiuyang Jiang; Hai Cheng; Chuan-Chou Shen; Yu-Min Chou (Global and Planetary Change, 2025)

Morphological engineering of single-crystal and polycrystalline ultrahigh-Ni cathodes composites for enhanced structural and electrochemical stability - Yiya Wang; Wenjun Shen; Jinyang Dong; Yun Lu; Yibiao Guan; Jianan Hao; Ning Li; Qing Huang; Yuefeng Su; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

Aptamer-anchored hydrophobic nanopores for electrochemical/fluorescent dual-mode identification of pathogenic bacteria - Jiangxue Dong; Tianyi Lu; Yufan Zhang; Ming Su; Jingjing Wang; Yajie Fan; Yanlei Li; Hongyuan Yan; Shigang Shen; Qun Ma; Zhongfeng Gao (Chemical Engineering Journal, 2025)

Enhancing the catalytic efficiency and thermostability of NADH oxidase by a multi-strategy computational approach - Taisong Shen; Yujiao Li; Hongling Shi; Baomin Luo; Zixing Dong; Yunchao Kan; Dandan Li; Lunguang Yao; Cunduo Tang (World Journal of Microbiology and Biotechnology, 2025)

Grazing mediates soil nutrient stocks through changing the plant functional composition and plant biomass allocation in alpine grassland - Fengcai He; Shikui Dong; Chunhui Ma; Xinghai Hao; Hao Shen; Juejie Yang; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Evolutionary history of a paleo-oxbow lake in the Yellow River within the Zoige Basin, NE Tibetan Plateau - Pengpeng Cao; Yuzhu Zhang; Yan Zhu; Ninglian Wang; Chun Chang Huang; Xiaohui Shi; Jiangli Pang; Yuqin Li; Jinpeng Zhou; Sikai Wang; Yao Jin; Mengting Li; et al. (Quaternary International, 2025)

Activation of molecular oxygen over MnOX/CeO2 for catalytic wet air oxidation of high-concentrated phenolic pollutants - Li Zhao; Haiping Mao; Yuanjing Lai; Jinsong He; Dong Tian; Mei Huang; Yongjia Lei; Fei Shen; Jianmei Zou (Journal of Environmental Management, 2025)

Multi-Scale study on combustion acceleration and Self-Catalytic mechanisms of Nickel-Based energetic complex [Ni(N2H4)2](N3)2 - Cheng Dong; Shiyong Chen; Lixiao Shen; Tu Xu; Yinning Zeng; Yan Li; Zhenxin Yi; Chenguang Zhu; Lin Zhang; Shunguan Zhu (Fuel, 2025)

Standard strategy for developing multicomponent nanopesticides: From gene function analysis to co-delivery nano-platform construction - Qinhong Jiang; Min Dong; Lin Che; Che Li; Xian Zhang; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Novel furfuryl-based phosphaphenanthrene containing N/P flame retardant: towards epoxy resin with excellent flame retardancy, enhanced toughness and low dielectric constant - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Unveiling sources and fate of sulfate in lake-groundwater system combined Bayesian isotope mixing model with radon mass balance model - Shen Qu; Yuanzhen Zhao; Muhan Li; Xiaohui Ren; Chenyu Wang; Xu Yang; Yanling Hao; Shaogang Dong; Ruihong Yu (Water Research, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Synergistic effect of hollow n-Al/H-MoO3 in the gas-phase reaction zone of solid propellant - Shuping Li; Cheng Dong; Xuan Qi; Shiyong Chen; Lixiao Shen; Yinning Zeng; Yan Li; Zhenxin Yi; Lin Zhang; Shunguan Zhu (Fuel, 2025)

Mitigating waterlogging-induced yield loss in cotton through removal of early fruits: Agronomic and physiological mechanisms - Yanjun Zhang; Shen Qiu; Tiantian Liang; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Red mud-based magnetic biochar composite as a peroxydisulfate activator for tetracycline degradation - Chao Shen; Xinxin Dong; Jing Yang; Yafei Li; Shihai Cui; Dapeng Zhang; Xiaochen Lin (Environmental Research, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Effect of Seismic Bedrock Interface Depth on Surface Ground Motion Parameters of Deep Overburden Sites - Yiyao Shen; Xiuli Du; Liyun Li; Dong-Mei Zhang (Journal of Earth Science, 2025)

High-efficiency ammonium recovery and high biomass yield from ultrahigh-ammonium industrial effluent via online-controlled photo-fermentation with thermoacidophilic Galdieria sulphuraria - Yu Li; Dong Wei; Xiannan Peng; Hao Shen; Li Ni; Guoyou Wei (Algal Research, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Rotational grazing can enhance the soil available nutrients rather than plant diversity to promote ANPP of alpine steppe - Fengcai He; Shikui Dong; Juejie Yang; Xinghai Hao; Chunhui Ma; Hao Shen; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Biocontrol effects of volatile organic compounds released from Burkholderia sola NAU20 to strawberry anthracnose caused by Colletotrichum gloeosporioides - Dongming Wang; Zhitao Geng; Jiming Shen; Tingting Xie; Fan Wu; Yu Zhang; Yiwei Dong; Dongmei Mao; Yanling Ji; Yan Huang; Zhoukun Li; Yongheng Liang; et al. (Postharvest Biology and Technology, 2025)

Risk prioritization and experimental validation of per- and polyfluoroalkyl substances (PFAS) in Chaohu Lake: Based on nontarget and target analyses - Wei Chang; Shen-Dong Xu; Ting Liu; Lan-Lan Wu; Si-Ting Liu; Gang Liu; Jian Sun; Ye-Xin Luo; Lei Gao; Hao Li; Qi Lu; Zhi Yuan; et al. (Journal of Hazardous Materials, 2025)

Health risks of ambient polycyclic aromatic hydrocarbons based on the prediction of their gas-phase concentrations in the central Yangtze River Delta, China: Regional and time-resolved variability - Wanqing Qi; Wei Feng; Xiangyu Zhang; Guihong Dong; Guofeng Shen; Zhijuan Shao; Ke Li; Hong Liao; Yuhang Wang; Mingjie Xie (Journal of Hazardous Materials, 2025)

Subchronic ozone exposure leads to multi-organ injuries with differential reversibility in male C57BL/6 J mice - Miao Li; Shen Chen; Xinhang Jiang; Lizhu Ye; Yuzhi Guo; Wenxue Li; Jiahao Zhang; Wenjie Liu; Yahan Yang; Zehua Ou; Liping Chen; Guanghui Dong; et al. (Journal of Hazardous Materials, 2025)

Unveiling the mechanism of fermentation induced antioxidant activity enhancement in asparagus juice: Metabolomic and transcriptomic insights into the functional role of Lactiplantibacillus plantarum JGS 49 - Jinqing Huang; Li Wang; Xue Li; Yao Zhang; Bo Dong; Shuai Hu; Cailing Liu; Dongwen Fu; Lecheng Shen; Guangxian Liu (Food Bioscience, 2025)

Enhanced dechlorination and degradation of Aroclor 1260 by resuscitation-promoting factor under alternating anaerobic-aerobic conditions: Superior performance and associated microbial populations - Sijia Fei; Xiaonan Li; Zhen Han; Faqian Sun; Xiao Xiao; Feng Dong; Chaofeng Shen; Xiaomei Su (Environmental Research, 2025)

Recycling paper packaging waste into Fe-biochar pellet catalyst for tetracycline degradation via peroxymonosulfate activation - Li Zhao; Kangting Du; Mei Huang; Dong Tian; Jinsong He; Yongjia Lei; Yan Liu; Guochun Lv; Jianmei Zou; Fei Shen (Environmental Research, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Hydrogel-anchored caffeic acid-copper ions coating: Integrated defensive and offensive strategy for synergistic antifouling - Jingyu Niu; Yiming Li; Yun Shen; Shideng Yuan; Dong Wang; Peijun Zheng; Zhining Wang (Chemical Engineering Journal, 2025)

Corrigendum to “Fucoidan from Ascophyllum nodosum and attenuate SARS-CoV-2 infection and by suppressing ACE2 and alleviating inflammation” [Carbohydr. Polym. 332 (2024) 121884] - Fang-Shu Shi; Yv-Hao Xie; Yong-Le Yang; Ling-Dong Xu; Jin-Jun Li; Xin Wang; Li-Ying Zhu; Wei-Wei Wang; Pei-li Shen; Yao-Wei Huang; Xiao-Qiong Li (Carbohydrate Polymers, 2025)

Clinical biomarkers of perioperative neurocognitive disorder: initiation and recommendation - Jianhui Liu; Cheng Li; Junyan Yao; Lei Zhang; Xuan Zhao; Xin Lv; Zhiqiang Liu; Changhong Miao; Yingwei Wang; Hong Jiang; Weifeng Yu; Tianlong Wang; et al. (Science China Life Sciences, 2025)

Harnessing the MYB51/SWEET20 module to increase soybean yield by facilitating sugar supply to sink organs - Jiafang Shen; Dong Cao; Songli Yuan; Qingnan Hao; Hongli Yang; Yi Huang; Lihong He; Jialing Yuan; Zhonglu Yang; Shuilian Chen; Zhihui Shan; Wei Guo; et al. (Plant Cell Reports, 2025)

Investigating the Potential Therapeutic Targeting of the JAK-STAT Pathway in Cerebrovascular Diseases: Opportunities and Challenges - Jia-Wei Wu; Bing-Xin Wang; Li-Ping Shen; Yong-Lin Chen; Zhi-Yong Du; Shi-Qing Du; Xiao-Jie Lu; Xu-Dong Zhao (Molecular Neurobiology, 2025)

Disruptions of white matter in adolescents with internet game disorder: evidence from seed-based d mapping - Hao Zheng; Chunyu Dong; Yu Wan; Hailong Shen; Sen Li; Shanling Ji; Jian Cui; Kun Li; Hao Yu; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

Impact of residential morphology on outdoor thermal comfort and building energy consumption in winter and summer: A case study - Minghao Wang; Yichen Dong; Wei Liao; Bo Pan; Sensheng Li; Junchao Duan; Shen Xu (Urban Climate, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Effects of early-life F-53B exposure on thyroid function in juvenile rats: The role of the cAMP signaling pathway - Shen-Pan Li; Wen-Hui Zhao; Jing Zhang; Wen-Ting Jiang; Jia-Yi Zhu; Yi-Xin Luo; Ping Xiang; Michael Bloom; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Effects of co-exposure to heat and ozone on lipid metabolism in the liver and adipose tissue of C57BL/6J male mice - Xinhang Jiang; Miao Li; Wenxue Li; Yuzhi Guo; Jiahao Zhang; Lizhu Ye; Zhanyu Guo; Yahan Yang; Wenjie Liu; Liping Chen; Qing Wang; Weidong Wu; et al. (Journal of Hazardous Materials, 2025)

Two-phase remediation of extreme textured soils: Integrating stabilized sludge and plant-assisted strategies for enhanced water-nutrient supply and nitrogen fixation - Jun Gao; Haining Tian; Lei Li; Danni Shen; Bin Dong; Zuxin Xu (Journal of Environmental Management, 2025)

Exploring the colorimetric sensing mechanism of metal porphyrin on the degree of roasting from the perspective of density functional theory - Shuai Dong; Yifan Zuo; Yongning Wei; Qianfeng Yang; Jingfei Shen; Kun Liu; Chuxuan Huang; Qianying Dai; Jingming Ning; Luqing Li (Food Chemistry, 2025)

Soil quality evaluation and limiting factor analysis in different microtopographies of hilly and gully region based on minimum data set - Linfu Liu; Fucang Qin; Yan Sheng; Long Li; Xiaoyu Dong; Shangxuan Zhang; Conglin Shen (CATENA, 2025)

Short-term P addition weakens the positive effects of N addition on CH4 uptake in alpine grasslands of the Qinghai-Tibetan Plateau - Jiannan Xiao; Shikui Dong; Hao Shen; Ran Zhang; Hang Shi; Fencai He; Wei Li; Xiaoyan Li (Plant and Soil, 2025)

Cortical thickness alternation in obsessive-compulsive disorder patients compared with healthy controls - Chunyu Dong; Hao Zheng; Hailong Shen; Yu Wan; Yinghong Xu; Ying Li; Liangliang Ping; Hao Yu; Chuanxin Liu; Jian Cui; Kun Li; Cong Zhou (Brain Imaging and Behavior, 2025)

G protein-coupled receptor GPR182 negatively regulates sprouting angiogenesis via modulating CXCL12-CXCR4 axis signaling - Changsheng Chen; Wei Liu; Fang Yuan; Xiaoning Wang; Xi Xu; Chang Chun Ling; Xiaojuan Ge; Xiaozhong Shen; Bowen Li; Yuqian Shen; Dong Liu (Angiogenesis, 2025)
Angiogenesis is a critical process for tumor progression, regulated by various signaling pathways. Although antiangiogenic therapies targeting the VEGF pathway have shown potential, their effectiveness is inconsistent across different tumor types. GPR182, an endothelial cell-specific G protein-coupled receptor, is frequently downregulated in hypervascular tumors, but its specific role in angiogenesis has not been well defined. Our study reveals that GPR182 expression is markedly reduced in hepatocellular carcinoma (HCC) and inversely correlates with CD31, a pan-endothelial marker. In zebrafish embryos, Gpr182 deficiency resulted in enhanced angiogenic sprouting and hypervascularization, and GPR182-deficient human umbilical vein endothelial cells (HUVECs) showed increased migration and proliferation. At the molecular level, GPR182 acts as a decoy receptor, binding CXCL12 and regulating its gradient, which in turn suppresses CXCR4-mediated angiogenesis. The pharmacological blockade of CXCR4 with AMD3100 corrected the abnormal angiogenic phenotype in Gpr182-deficient zebrafish embryos and in the livers of a zebrafish HCC model. This work uncovers GPR182 as a negative regulator of angiogenesis, a key process in tumor growth and metastasis, and proposes that targeting GPR182 may offer a novel therapeutic approach for antiangiogenic strategies in cancer treatment.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Lead seasonality: Affect children’s blood lead levels and implication for lead exposure prevention - Jie Dong; Xiaoping Li; Yu Zhang; Xueming Zheng; Shuang Zhang; Qishang Zhou; Feng He; Danqian Shi; Yueheng Jiang; He Shen; Xu Zhang; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

Research on optimal scheduling and carbon revenue distribution strategy of “source-grid-load-storage” projects based on CCER methodology - Xudong Li; Zhongfu Tan; Junyao Shen; Xinyue Dong; He Wang; Xin Qi (Journal of Environmental Management, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Four new constituents from the fruits of Cyclocodon lancifolius (Roxburgh) Kurz - Meng-Jie Ma; Wei Wu; Bei Tian; Li-Ping Shen; Tong Wu; Chun-Yue Huang; Xu-Dong Mao; Xiao Hu (Natural Product Research, 2025)

Fuzzy-based method for seismic soil structure interaction and performance evaluation of subway stations - Yiyao Shen; M. Hesham El Naggar; Dong-Mei Zhang; Liyun Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2025)

Exceptional visible-light photocatalytic activity induced by lattice distortion in medium-entropy perovskite oxide La0.5Sr0.5Fe0.5Ti0.5O3 - Hongfang SHEN; Congcong MA; Zhihong QI; Jiaqi DING; Dong LI; Bo MA; Xiao ZHANG; Guozhong CAO; Youjun LU (Journal of Environmental Chemical Engineering, 2025)

Hybrid crosslinking cellulose nanofibers-reinforced zwitterionic poly (ionic liquid) organohydrogel with high-stretchable, anti-freezing, anti-drying as strain sensor application - Dong Fu; Linhui Xing; Yang Xie; Peng Li; Fan Yang; Xin Sui; Jiaying Liu; Jialong Chi; Bo Huang; Jun Shen (Carbohydrate Polymers, 2025)

Retraction notice to “Heterogeneity of biochar amendment to improve the carbon and nitrogen sequestration through reduce the greenhouse gases emissions during sewage sludge composting” [Bioresour. Technol. 224 (2017) 428−438] - Mukesh Kumar Awasthi; Meijing Wang; Hongyu Chen; Quan Wang; Junchao Zhao; Xiuna Ren; Dong-sheng Li; Sanjeev Kumar Awasthi; Feng Shen; Ronghua Li; Zengqiang Zhang (Bioresource Technology, 2025)

Efficient biodegradation of flurochloridone herbicide by Streptomyces parvus strain F-G-2 and its degradation mechanism - Dong Zhao; Shuo Shen; Junlong Feng; Shuqun Deng; Enyu Lu; Chenxu Gao; Yang Zhang; Hongyu Chen; Wei Li (Bioresource Technology, 2025)

Enhanced methane production through synergistic integration of quorum sensing Signals and microbial electrolysis in anaerobic digestion of low-quality biomass - Xiayuan Wu; Shen Wang; Wanqi Zhao; Yonglan Xi; Shuhuan Li; Fengxue Xin; Weiliang Dong; Honghua Jia (Bioresource Technology, 2025)

First report of black mold caused by Diaporthe eres on Rosa multiflora in China - Dong Zhao; Junlong Feng; Shuqun Deng; Chenxu Gao; Shuo Shen; Hongyu Chen; Wei Li (Australasian Plant Pathology, 2025)
In Qinghai Province, China, the wild rose ( Rosa multiflora Thunb) has been identified as a critical host for a virulent strain of Diaporthe eres , which is implicated in the causation of the catastrophic black mold disease. A plant specimen, manifesting intense symptoms indicative of black mold, underwent a meticulous diagnostic process. Employing a combination of morphological assessments and nucleotide sequencing of key genetic markers—Internal Transcribed Spacer (ITS), Translation Elongation Factor 1-α (TEF1-α), Tubulin 2 (TUB2), Histidine biosynthesis (HIS3), and Calmodulin (CAL)—the pathogenic fungus was unequivocally identified as Diaporthe eres . The reisolation of this strain, adhering to the principles of Koch’s postulates, substantiated its etiological role in the black mold disease affecting wild roses. This study represents the inaugural documentation of Diaporthe eres infection and its pathological consequences in wild roses within the Chinese context, providing critical insights into the pathogen’s potential impact on native vegetation and shaping prospective strategies for disease management.

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Uniform Spray Dried Loxapine Microparticles Potentially for Nasal Delivery: Exploring Discriminatory In Vitro Release Evaluation Methods - Mengyuan Li; Ziwei Nie; Shen Yan; Shengyu Zhang; Xiao Dong Chen; Winston Duo Wu (The AAPS Journal, 2025)

Benzyl butyl phthalate promotes ferroptosis in Sertoli cells via disrupting ceruloplasmin-mediated iron balance - Yu Dong; Shuge Shu; Xiangyu Yu; Xinting Chen; Qiong Li; Xiaobing Shen; Yongquan Yu (Toxicology, 2025)

cTAGE5 is involved in the assembly of Golgi ring in mouse primordial follicle - Haowei Wu; Yaqing Wang; Jiayi Li; Yan Qin; Min Chen; Zhiming Shen; Fangfang Dong; Xiuhong Cui; Liang Liu; Zhiheng Xu; Fei Gao (Science Bulletin, 2025)

BWO-CAformer: An improved Informer model for AQI prediction in Beijing and Wuhan - Xu Dong; Deyi Li; Wenbo Wang; Yang Shen (Process Safety and Environmental Protection, 2025)

Emission factors and driving forces of provincial-level CO2 from electricity production and consumption in China from 2013 to 2020 - Ruoxi Xiong; Chenling Fu; Huimin Chang; Nan Li; Shen Qu; Dong Zhao; Changqing Xu; Jianchuan Qi; Ming Xu (Journal of Environmental Management, 2025)

Various wind activity proxies unmixed from grain-size distributions of surface eolian sands at the desert scale in the Tengger Desert, Northwest China - Shipei Dong; Zhuolun Li; Qiujie Chen; Yingyibing Shen; Xuehua Che; Cheng Zhang; Yinzhou Huang (Geomorphology, 2025)

LPA reduces the apoptosis of cryopreserved porcine skin-derived stem cells by inhibiting the regulatory factor TNF-α - Xin-Xiang Xie; Jia-Dong Sun; Ming-Xin Zang; Geng Zhang; Chun-Xiao Li; Xiang-Wei Zhai; Wei Shen; Wei Ge; Shun-Feng Cheng (Cryobiology, 2025)

The •OH-induced direct ammonia oxidation pathway for nitric acid photosynthesis - Xin Li; Jielin Wang; Jieyuan Li; Chunling Zhang; Ruimin Chen; Shujie Shen; Yanjuan Sun; Lili Zhang; Fan Dong (Chemical Engineering Journal, 2025)

Combined effects of the visual-thermal environment on restorative benefits in hot outdoor public spaces: A case study in Shenzhen, China - Wen DONG; Donghui DAI; Mei LIU; Yaowu WANG; Shuang LI; Pengyuan SHEN (Building and Environment, 2025)

Assessing the predicted impact of single amino acid substitutions in MAPK proteins for CAGI6 challenges - Paola Turina; Maria Petrosino; Carlos A. Enriquez Sandoval; Leonore Novak; Alessandra Pasquo; Emil Alexov; Muttaqi Ahmad Alladin; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Jianlin Cheng; et al. (Human Genetics, 2025)

Assessing the predicted impact of single amino acid substitutions in calmodulin for CAGI6 challenges - Paola Turina; Giuditta Dal Cortivo; Carlos A. Enriquez Sandoval; Emil Alexov; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Piero Fariselli; Lukas Folkman; Akash Kamandula; Panagiotis Katsonis; et al. (Human Genetics, 2025)

The isolation, identification, whole-genome sequencing of Trichoderma brevicompactum TB2 and its effects on plant growth-promotion - Hao Li; Zuohereguli Kuerban; Rou Jiang; Feixue He; Xiao Hu; Yangchun Xu; Caixia Dong; Qirong Shen (Plant and Soil, 2025)

Dynamic analysis of intrahepatic T cells reveals a unique group of restorative Cxcr3+ tissue-resident CD4 T cells in acute liver injury - Shen-Xi Ouyang; Yong-Gang Xu; Peng Ding; Yue Long; Zhen Zhang; Si-Jia Sun; Yan Zhang; Hang Yin; Jia-Bao Zhang; Qi Cao; Fu-Ming Shen; Pei Wang; et al. (Toxicology, 2025)

Methamphetamine inhibits huntingtin-associated protein 1-mediated tyrosine receptor kinase B endocytosis resulting the neuroprotective dysfunction of brain-derived neurotrophic factor - Baoyu Shen; Zhenling Wu; Mengran Lv; Genmeng Yang; Yuanyuan Cao; Yuan Zhang; Junjie Shu; Wenjuan Dong; Zhenping Hou; Di Jing; Xinjie Zhang; Yuhan Hou; et al. (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Large language models: game-changers in the healthcare industry - Bin Dong; Li Zhang; Jiajia Yuan; Yang Chen; Quanzheng Li; Lin Shen (Science Bulletin, 2025)

Adsorption behavior and mechanism insight of organoarsenic compounds on magnetic ion exchange resin based on the combined method of DFT calculation and characterization - Yuchen Gao; Wenlong Wu; Lei Shen; Jinhui Qu; Yan Li; Dongxiao Sun; Zhiqiang Dong; Lei Ding (Journal of Water Process Engineering, 2025)

Pollutants degradation performance and microbial response evaluation about expressway service area sewage treatment of continuous flow anoxic-oxic moving bed biofilm reactor system - Qi He; Qian Zhang; Meng Li; Hao-nan Shen; Jia-jing Chen; Dong Ni (Journal of Water Process Engineering, 2025)

Collaborative performance of enzymatic saccharification and organic pollutant degradation from PHP (phosphoric acid coupled with hydrogen peroxide) pretreatment of lignocellulose - Miao Lei; Xuan Dong; Mei Huang; Li Zhao; Jianmei Zou; Dong Tian; Yongjia Lei; Jinsong He; Fei Shen (Journal of Environmental Management, 2025)

Efficient biosynthesis of rare sugars using glycerol as a sole carbon source in metabolic engineered Bacillus subtilis - Kangqing Fei; Zhou Chen; Liqun Shen; Xiao-Dong Gao; Hideki Nakanishi; Zijie Li (Food Bioscience, 2025)

Microplastics release from infant feeding bottles and milk storage bags - Long Zhao; Yiying Gu; Hua Cai; Xin Xu; Jianguo Yu; Jing Li; Ying Shen; Leiyan Zhu; Yan Jin; Mei Zhang; Ruihua Dong; Bo Chen (Food Control, 2025)

The emerging roles of particulate matter-changed non-coding RNAs in the pathogenesis of Alzheimer's disease: A comprehensive in silico analysis and review - Hui-Xian Zeng; Shuang-Jian Qin; John Andersson; Shen-Pan Li; Qing-Guo Zeng; Jia-Hui Li; Qi-Zhen Wu; Wen-Jie Meng; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Guang-Hui Dong; et al. (Environmental Pollution, 2025)

Zero-carbon renewal of communities through collaborative retrofitting of multi-scale design elements: A case of Wuhan, China - Shen Xu; Huangwanjin Zhou; Yichen Dong; Qiuguo He; Gaomei Li (Energy and Buildings, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

Isolation and identification of two novel PDE-5 inhibitors illegally added to pressed candies - Li-Hong Zhao; Xiao-Pu Liu; Pei-Zhi Dong; Xin-Hua Xiang; Guo-Hua Shen (Food Additives & Contaminants: Part A, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

AM fungus plant colonization rather than an Epichloë endophyte attracts fall armyworm feeding - Youlei Shen; Jiming Yang; Ziyuan Ma; Yingde Li; Wanqing Dong; Tingyu Duan (Mycorrhiza, 2025)

Applicability of Different Indices for Delineating the Boundary of Arid Region: A Case Study in Northwestern China - Xue Peng; Xiang Li; Yingyibing Shen; Xuehua Che; Shipei Dong; Zhuolun Li (Journal of Earth Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Antibacterial Effect and Network Pharmacology Mechanism of Male Bombyx mori. on Escherichia Coli - Mengqing Guo; Ning Dong; Chunxue Liu; Rui Ma; Shen Li; Yao Sun (International Journal of Peptide Research and Therapeutics, 2025)

Outdoor light at night exposure was associated with hypothyroidism in pregnant women: A national study in China - Hong-Xing Zou; Li-Wen Hu; Zheng Zhang; Alexander E.P. Heazell; Xueran Wang; Wentao Yue; Xiao-Fan Lu; Xiao-Yi Liu; Shuo Zhang; Le-Bing Wang; Enjie Zhang; Shaofei Su; et al. (Science of The Total Environment, 2025)

Spatiotemporal evolution and influencing mechanism of urbanization and ecological environmental quality between 2000 and 2020 in Henan Province, China - Xinyu Dong; Kaijian Xu; Wei Li; Qingjiu Tian; Qingchu Fan; Siwen Fang; Jiayi Shen; Mengya Jia; Jia Tian (Remote Sensing Applications: Society and Environment, 2025)

Corrigendum to “Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis” [J Hazard Mater 468 (2024) 133836] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2025)

Simultaneous detection of mixed colorants adulterated in black tea based on various morphological SERS sensors - Qingqing Cui; Jingfei Shen; Huiyan Jia; Tiehan Li; Shuci Cao; Shuai Dong; Yuming Wei; Li Zou; Yurong Chen; Yujie Wang; Jingming Ning; Luqing Li (Food Research International, 2025)

Enzyme-functionalized polymer foams for boosting CO2 bioconversion of microalgae in flow bioreactors - Shaobin Zhang; Yuan Wen; Zhonglin Li; Qikai Tian; Juan Li; Haixia Shen; Jing Zhang; Chenjie Zhu; Weiliang Dong; Ziyi Yu (Chemical Engineering Journal, 2025)

Prediction of the height of water-conducting fracture zone using the FA-ALO-SVR model - Yaoshan Bi; Shuhao Shen; Jiwen Wu; Dong Li (Earth Science Informatics, 2025)

Simultaneous nitrification and denitrification in the treatment of expressway service sewage using the SBBR system at varying aeration rates: Transitioning from simple to complex interspecies relationships - Dong Ni; Bin Tan; Xun-hao Liu; Meng Li; Qi He; Hao-nan Shen; Jia-jing Chen; Qian Zhang (Journal of Water Process Engineering, 2024)

Phosphorus deficiency promotes root:shoot ratio and carbon accumulation via modulating sucrose utilization in maize - Zu-Dong Xiao; Zhen-Yuan Chen; Yi-Hsuan Lin; Xiao-Gui Liang; Xin Wang; Shou-Bing Huang; Sebastian Munz; Simone Graeff-Hönninger; Si Shen; Shun-Li Zhou (Journal of Plant Physiology, 2024)

Construction of C3N4/Ag2S p-n semiconductor heterojunction coupled with Ag-induced SPR effect on CF cloth for improving photocatalytic activity - Qingquan Xue; Kaiwei Hu; Qian Feng; Hao Lin; Minuo Dong; Kashif Hayat; Yang Zhang; Xiaofeng Shen; Shijie Li (Journal of Environmental Chemical Engineering, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Investigation of the impact load characteristics of micro-jet induced by cavitation collapse on rigid wall surface - Xiaobo Shen; Wei Han; Rennian Li; Shiqi Yang; Haozhi Nan; Lu Bai; Yifan Dong (Chemical Engineering Journal, 2024)

A cascaded process to upgrade bleached bamboo pulp into dissolving pulp and arabinoxylan - Qiongyao Su; Daizunyan He; Jianping Luo; Xiaowen Zhou; Shiyu Wu; Li Zhao; Fei Shen; Jinguang Hu; Dong Tian (Carbohydrate Polymers, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Research on intensive nitrogen removal of municipal sewage by mainstream anaerobic ammonia oxidation process - Haonan Shen; Qian Zhang; Meng Li; Xibei Tan; Xiaoqian Dong; Hongyu Wang (Chemosphere, 2024)

Leaching behavior of microplastics during sludge mechanical dewatering and its effect on activated sludge - Xingfeng Yang; Shiyu Niu; Man Li; Yulong Niu; Kailiang Shen; Bin Dong; Jin Hur; Xiaowei Li (Water Research, 2024)

Radar forward modeling and intelligent identification of shallow subgrade defects - Li Xin; Chen Han-qing; Liu Chen-yang; Su Dong; Chen Xiang-sheng; He Bo-hu; Shen Xiang (Transportation Geotechnics, 2024)

Different responses of individuals, functional groups and plant communities in CSR strategies to nitrogen deposition in high-altitude grasslands - Xueqi Li; Ying Li; Hao Shen; Shuai Li; Zhenzhen Zhao; Jiannan Xiao; Ran Zhang; Hang Shi; Hui Zuo; Tu Danjia; Guoming Chen; Xueli Zhou; et al. (Science of The Total Environment, 2024)

Green synthesis of diatom–allophane bio-nanocomposites for highly efficient oxytetracycline adsorption - Mengyuan Li; Shun Wang; Dong Liu; Dusan Losic; Ning Zhao; Qian Tian; Yuguo Shen; Rongda Yu; Hao Liu; Qiyi Ma; Peng Yuan (Science of The Total Environment, 2024)

Highly emissive white single-molecular material towards organic light-emitting transistors - Dan Liu; Ziyi Xie; Zhagen Miao; Chenguang Li; Molin Shen; Pu Wang; Qingbin Li; Can Gao; Wenping Hu; Huanli Dong (Science Bulletin, 2024)

Specialists regulate microbial network and community assembly in subtropical seagrass sediments under differing land use conditions - Weiguo Zhou; Xiaomei Shen; Zhimeng Xu; Qingsong Yang; Mengyu Jiao; Hanying Li; Li Zhang; Juan Ling; Hongbin Liu; Junde Dong; Anning Suo (Journal of Environmental Management, 2024)

Corrigendum to “Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the industrial revolution recorded by high-resolution stalagmites” [Global and Planetary Chang, 232 (2024) 104337] - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Rapid fluorescence detection of black tea fermentation degree based on cobalt ion mediated carbon quantum dots - Shuci Cao; Shuai Dong; Yurong Chen; Jingfei Shen; Qingqing Cui; Changying Sun; Jingming Ning; Luqing Li (Food Control, 2024)

Scorpion-inspired multi-scale contact enabled multifunctional piezoresistive pressure sensor based on hybrid nanofiber decoration - Xiaoyue Ren; Ruixue Li; Hao-Yang Mi; MiaoMiao Zhang; Qingli Tian; Xin Jing; Xiaoshuai Zhu; Jian Han; Yue Ren; Binbin Dong; Chongzhao Zhang; Chuntai Liu; et al. (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Interactions between fibroblasts and monocyte-derived cells in chronic lung injuries induced by real-ambient particulate matter exposure - Youjin Zeng; Rui Zhang; Yue Jiang; Daochuan Li; Liping Chen; Guanghui Dong; Rong Zhang; Yujie Niu; Wen Chen; Shen Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Lattice matched Z-scheme ZnIn2S4/Ag3PO4 enhanced photocatalytic performance by controlling morphology synthesis - Zhenyu Fu; Kai Ye; Zhenyou Dong; Suyun Li; Huilin Zhou; Sihang Xia; Longxiang Shen; Wenyan Shi (Journal of Environmental Chemical Engineering, 2024)

Sulfadiazine detection in aquatic products using upconversion nanosensor based on photo-induced electron transfer with imidazole ligands and copper ions - Shen Zhang; Shuhua Li; Dong Li; Jizhong Wu; Tianhui Jiao; Jie Wei; Xiaomei Chen; Qingmin Chen; Quansheng Chen (Food Chemistry, 2024)

Mechanism of Lacticaseibacillus rhamnosus JY027 alleviating hyperuricemia in mice through gut-kidney axis - Chao Miao; Kai Dong; Yu Shen; Yilin Sun; Wenyan Li; Chaoxin Man; Yu Zhang; Qianyu Zhao; Yujun Jiang (Food Bioscience, 2024)

Corrigendum to “Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig” [Environ. Pollut. 329 (2023) 121729] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2024)

Biomass burning records of the Shulehe Glacier No. 4 from Qilian Mountains, Northeastern Tibetan Plateau - Quanlian Li; Yao Li; Ninglian Wang; Tanuj Shukla; Xiaobo Wu; Xiunan Yao; Shijin Wang; Xin Wan; Pengfei Chen; Huan Zhang; Baoshou Shen; Zhiwen Dong; et al. (Environmental Pollution, 2024)

Biomimetic solar evaporator for continuous clean water production with synergistic organic dye wastewater remediation - Peng Zhao; Jialu Xu; Jiakai Li; Meng Xia; Tao Yang; Guang Liu; Jiahui Yu; Qi Chen; Yijun Shen; Meng Li; Dong Wang; Juanxiu Xiao (Desalination, 2024)

Cascade catalyzed dual-responsive Gold-Ferri “bomb-like” nanoreactors for positive feedback penetrating in sequential targeted triple glioblastoma therapy - Qiyue Wang; Xiaofei Gu; Ji Liu; Yan Zhao; Zhen Li; Shuyan He; Dong Shen; Xiaofei Xin; Yan Shen (Chemical Engineering Journal, 2024)

Revealing the intensification effect of circulating hydrothermal pretreatment: A sustainable route for biorefinery - Feiyue Shen; Chenjun He; Yuhang Wang; Jiayi Xu; Mei Huang; Li Zhao; Jinguang Hu; Dong Tian; Fei Shen (Chemical Engineering Journal, 2024)

Synergistic engineering of Ag doping and P vacancies in nanoflower-like Ni2P for acrylamide-assisted electrolysis of seawater splitting - Dan Zhang; Zeyi Zhang; Lingshen Meng; Limei Dong; Yun Shen; Zhining Wang; Yiming Li (Chemical Engineering Journal, 2024)

Fabrication of Uniform Melatonin Microparticles Potentially for Nasal Delivery: A Comparison of Spray Drying and Spray Freeze Drying - Chengzhi You; Shen Yan; Mengyuan Li; Shuaiyu Xie; Shengyu Zhang; Xiao Dong Chen; Winston Duo Wu (Pharmaceutical Research, 2024)

Selenium Improves Arsenic-Induced Male Reproductive Dysfunction by Regulating H3K14ac Level - Dunxuan Yuan; Kaina Shen; Xiuxia Dong; Yan Yang; Bohe Wang; Xiaojuan Feng; Fang Li; Xinrui Zhao; Fangzhou Tian; Jinrou Quan; Junling Wang; Xiangli Li (Biological Trace Element Research, 2024)

Microbial regulatory mechanisms of disease-resistant tobacco varieties in the prevention and control of bacterial wilt disease - Hao Xia; Jia Shen; Muhammad Riaz; Huaying Yang; Qing Dong; Chaolong Zu; Fei Yu; Yifeng Yan; Jiaxin Li; Bo Liu; Chaoqiang Jiang (Applied Soil Ecology, 2024)

Photoelectron‐promoted metabolism of sulphate‐reducing microorganisms in substrate‐depleted environments - Chao Zhong; Anhuai Lu; Hailiang Dong; Shan Huang; Liang Shi; Yanan Shen; Yangjian Cheng; Yiran Dong; Xiangzhen Li; Jie Xu; Jinren Ni; Michael F. Hochella; et al. (Environmental Microbiology, 2024)
Sulphate‐reducing microorganisms, or SRMs, are crucial to organic decomposition, the sulphur cycle, and the formation of pyrite. Despite their low energy‐yielding metabolism and intense competition with other microorganisms, their ability to thrive in natural habitats often lacking sufficient substrates remains an enigma. This study delves into how Desulfovibrio desulfuricans G20, a representative SRM, utilizes photoelectrons from extracellular sphalerite (ZnS), a semiconducting mineral that often coexists with SRMs, for its metabolism and energy production. Batch experiments with sphalerite reveal that the initial rate and extent of sulphate reduction by G20 increased by 3.6 and 3.2 times respectively under light conditions compared to darkness, when lactate was not added. Analyses of microbial photoelectrochemical, transcriptomic, and metabolomic data suggest that in the absence of lactate, G20 extracts photoelectrons from extracellular sphalerite through cytochromes, nanowires, and electron shuttles. Genes encoding movement and biofilm formation are upregulated, suggesting that G20 might sense redox potential gradients and migrate towards sphalerite to acquire photoelectrons. This process enhances the intracellular electron transfer activity, sulphur metabolism, and ATP production of G20, which becomes dominant under conditions of carbon starvation and extends cell viability in such environments. This mechanism could be a vital strategy for SRMs to survive in energy‐limited environments and contribute to sulphur cycling.

The Role of miRNA in Hyperthyroidism Induced by Excessive Iodine in Drinking Water - Zhihan Yang; Yishan Dong; Shuo Wang; Jing He; Zheng Shen; Jin Cheng; Jinyu Li; Qiaoling Liu; Ziqi Xu; Dianjun Sun; Wei Zhang (Biological Trace Element Research, 2024)

A rotated rice spike detection model and a crop yield estimation application based on UAV images - Yunting Liang; Huifen Li; Han Wu; Yinwei Zhao; Zhijie Liu; Dong Liu; Zongru Liu; Gangao Fan; Zhaoyang Pan; Zhuo Shen; Jia Lv; Jiyu Li (Computers and Electronics in Agriculture, 2024)

Land-use intensification exerts a greater influence on soil microbial communities than seasonal variations in the Taihu Lake region, China - Ruonan Xiong; Dong Qian; Zijian Qiu; Yixin Hou; Qing Li; Weishou Shen (Science of The Total Environment, 2024)

Surface soil phytolith assemblages across an altitudinal transect in the Qilian Mountains of Northwestern China, and their implications for palaeoecologic analysis in arid alpine regions - Xiang Li; Shipei Dong; Zhuolun Li; Xue Peng; Yingyibing Shen; Qihang Jin; Xinhui Yu; Dezhong Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Synergistic activation mechanism of CO2 and H2O during preparation of Zhundong coal-based activated carbons for adsorption and reduction of NO - Hao Sun; Lianfei Xu; Yang Li; Fei Sun; Zhuozhi Wang; Mengchi Yang; Yao Dong; Wenwen Kong; Boxiong Shen; Xin Wang; Jiancheng Yang (Fuel, 2024)

Identification of crucial metabolites in colored grain wheat (Triticum aestivum L.) regulated by nitrogen application - Qiuyan Yan; Minmin Zhang; Yaqin Jia; Fei Dong; Yanting Shen; Feng Li (Food Research International, 2024)

Lipidomics and metabolomics reveal the molecular mechanisms underlying the effect of thermal treatment on composition and oxidative stability of walnut oil - Jing-Jing Zhang; Xiao Xu; Qin Zeng; Cong Li; Bo-Nan Xi; Yu Shu; Tianchen Ma; Hengtao Dong; Yehua Shen (Food Research International, 2024)

Synergistic optimization of the water state and transport pathway in hydrogels via pullulan and directional Freezing-Assisted salting out for efficient evaporation - Huanwei Shen; Xiayue Yang; Wenhao Li; Zhihua Sha; Hongmei Luo; Zixuan Li; Sihan Dong; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Comprehensive investigation of a dangerous counter-tilt landslide in the upper reaches of Jinsha River, China - Qiang Xu; Zhigang Li; Weihua Zhao; Weile Li; Xing Zhu; Xiujun Dong; Congwei Yu; Weimin Li; Xueqing Li; Xincheng Wang; Huiyan Lu; Shouyu Wang; et al. (Landslides, 2024)

Effects and Action Mode of Oleic Acid and Azone on Release and Penetration Process of Levothyroxine Sodium Patches - Xing Li; Kaili Liang; Yingying Dong; Shen Li; Zhengnan Gao; Qing Wang (AAPS PharmSciTech, 2024)

Polyacrylate modified Cu electrode for selective electrochemical CO2 reduction towards multicarbon products - Yuchuan Shi; Kaini Zhang; Chung-Li Dong; Ta Thi Thuy Nga; Miao Wang; Daixing Wei; Jialin Wang; Yiqing Wang; Shaohua Shen (Science Bulletin, 2024)

Experimental study on direct shear properties and shear surface morphologies of hydrate-bearing sediments - Yajuan Zhang; Yanlong Li; Mingtao Chen; Lin Dong; Zhiyang Jiang; Kaixiang Shen; Penghui Zhang; Nengyou Wu (Gas Science and Engineering, 2024)

Fabrication of a label-free electrochemical immunosensor by functionalized nanofiber membrane for the ultrasensitive detection of quinalphos - Jian-cheng Hu; Peng Wen; Yu Wang; Jin-yi Yang; Zhi-li Xiao; Zhen-lin Xu; Yu-dong Shen; Hong Wang; Bruce D. Hammock (Food Control, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Heterometallic Eu/Zn-MOF-based ratiometric sensing platform: Highly sensitive fluorescence / second-order scattering identification of tetracycline analogs and its molecular informatization applications - Ya Jie Fan; Jiang Xue Dong; Tan Liu; Yan Qing Chang; Yong Sen Zhao; Yan Lei Li; Sai Mei Zhang; Song Yun Cao; Ming Su; Shi Gang Shen; Zhong Feng Gao (Analytica Chimica Acta, 2024)

Three new chromones from the whole plants of Chamaecrista rotundifolia and their anti-rotavirus activities - Pei-Song Yang; Xin-Yan He; Shan-Shan Li; De-Quan Huang; Si-Yu Shen; Xiao-Shan Liu; Yue-Yu Ma; Miao Dong; Min Zhou; Feng-Xian Yang; Yin-Ke Li (Natural Product Research, 2024)

Seismic response characteristics of shield tunnel structures in liquefiable soils - Yiyao Shen; M. Hesham El Naggar; Dong-Mei Zhang; Liyun Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2024)

Insights of carbon reduction practices from Winter Olympics 2022 - Xiaoyong Liao; Shuai Zhong; Jie Huang; Zhu Liu; Ayman Elshkaki; You Li; Lei Shen; Yingli He; Li An; Yidong Zhu; Wenhao Sun; Tao Liang; et al. (Science Bulletin, 2024)

Sandy desertification monitoring with the Relative Normalized Silica Index (RNSI) based on SDGSAT-1 thermal infrared image - Ziyu Yang; Xiaosong Li; Tong Shen; Amos Tiereyangn Kabo-bah; Hanwen Cui; Xingxu Dong; Lei Huang (Remote Sensing of Environment, 2024)

Corrigendum to “Restoration actions associated with payment for ecosystem services promote the economic returns of alpine grasslands in China” [J. Clean. Prod. 458 (2024) 1–15, 142439] - Shikui Dong; Yudan Xu; Shuai Li; Hao Shen; Mingyue Yang; Jiannan Xiao (Journal of Cleaner Production, 2024)

Tracing the geographic origin of CTC black tea based on colorimetric sensor array response to taste substances combined with chemometrics - Jingfei Shen; Tiehan Li; Yurong Chen; Huan Zhou; Shuai Dong; Yuming Wei; Feilan Li; Jingming Ning; Luqing Li (Food Control, 2024)

Two sex pheromone receptors for sexual communication in the American cockroach - Na Li; Renke Dong; Huanchao Zeng; Yan Zhang; Run Huang; Wei Liu; Fengming Cao; Jincong Yu; Mingtao Liao; Jingyou Chen; Wenlei Zhang; Zejian Huang; et al. (Science China Life Sciences, 2024)

Brooding fathers actively consume viable embryos to take up nutrients in a monogamous syngnathid fish - Tingting Lin; Xin Liu; Siping Li; Dong Zhang; Fengyuan Shen (Frontiers in Marine Science, 2024)
Syngnathid fishes often experience a reduction in brood size and an increase in immunity during pregnancy. Researchers have studied the polygamous broad-nosed pipefish ( Syngnathus typhle ) and revealed that some eggs from low-quality females in the male’s brood pouch serve as nurse eggs that are absorbed by the father. It is unclear whether nurse eggs also exist in other syngnathid fishes, especially in monogamous syngnathid fishes. In monogamous syngnathid fishes, the male pouch only carries eggs from a single female. Thus, the question remains: do some eggs of monogamous syngnathid fishes also serve as nurse eggs? And if so, are these nurse eggs impaired eggs, or are they viable eggs that are consumed by the brooding father? In the present study, we used the monogamous lined seahorse ( Hippocampus erectus ) and asked whether nurse eggs exist in this species. We also explored whether nurse eggs potentially originate from viable versus inviable eggs. Using isotope labeling, we found that nutrients from embryos could be transferred to brooding fathers. Furthermore, we also found that brooding fathers with limited food had a higher isotope content and a smaller brood size compared to individuals with sufficient food. These results have demonstrated that nurse eggs exist in the lined seahorse, and also suggested that the brooding fathers actively consume viable embryos to absorb nutrients in response to low food availability. These findings help us better understand parent–embryo conflict, filial cannibalism, and male-only care in teleost fishes.

Rhizosphere microbes influence wogonoside accumulation in perennial Scutellaria baicalensis - Yang SUN; Hong LIU; Junwei PENG; Minchong SHEN; Yang HU; Dongsheng YU; Jiangang LI; Yuanhua DONG (Pedosphere, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

Middle Ordovician shallow-water gastropods from southern Xizang (Tibet), China - Wen-Jie Li; Xiang Fang; Shen-Yang Yu; Clive Burrett; Yong Yi Zhen; Jia-Yuan Huang; Yuan-Dong Zhang (Palaeoworld, 2024)

Restoration actions associated with payment for ecosystem services promote the economic returns of alpine grasslands in China - Shikui Dong; Yudan Xu; Shuai Li; Hao Shen; Mingyue Yang; Jiannan Xiao (Journal of Cleaner Production, 2024)

Effect of solid-state fermentation on the nutritional composition and physicochemical properties of whole-grain highland barley and the application in digestive cookies - Shunzhang Ma; Jilin Dong; Jiayao Li; Yingying Zhu; Yunlong Li; Ruiling Shen (Food Bioscience, 2024)

A mesoporous magnetothermal nanopomegranate with acid-tolerant hierarchical structure for remote controlled drug delivery - Yanxia Yang; Yingzi Li; Xin Xia; Shengkai Li; Shen Wang; Liang Zhang; Yuqi Cheng; Long Chen; Qian Dong; Zhuo Chen (Chemical Engineering Journal, 2024)

Creating a zero amylose barley with high soluble sugar content by genome editing - Yun Li; Yanyan Jiang; Dong Cao; Bin Dang; Xijuan Yang; Shiting Fan; Yuhu shen; Genying Li; Baolong Liu (Plant Molecular Biology, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

Formulation and Characterization of Ethosomes for Transdermal Delivery of Prinsepia Utilis Rogle Seed Oil with Ameliorative Effects against UVB-Induced Skin Damage - Qianqian Fang; You Li; Fei Xiong; Xiaolong Hu; Ying Song; Wenbing Shen; Haijuan Dong; Xinhong Shi; Hao Wang (AAPS PharmSciTech, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Corrigendum to “Improvement of protein structural and functional properties of indica-japonica hybrid rice by radio frequency treatment” [90 (2023) 103516] - Yifei Dong; Yan Cui; Xiaoting Xian; Ling Zhang; Jiafeng Shen; Jiangang Ling; Suhong Li (Innovative Food Science & Emerging Technologies, 2024)

Immunomodulatory gallium/glycyrrhizic acid hydrogels for treating multidrug-resistant Pseudomonas aeruginosa-infected pressure ulcers - Chaofan Zhang; Erya Cai; Xiaoliang Qi; XinXin Ge; Yajing Xiang; Jiajia Wang; Ying Li; Lizhang Lv; Hui Zheng; Yuna Qian; Wei Dong; He Li; et al. (Chemical Engineering Journal, 2024)

Unraveling the C–C coupling mechanism on Ni–O–Fe asymmetric sites for photocatalytic nonoxidative coupling of methane - Huimin Li; Zhe Sun; Chenlong Dong; Xueli Zhang; Chengkun Lei; Baobao Jin; Qianqian Shen; Husheng Jia; Jinbo Xue (Chemical Engineering Journal, 2024)

Fucoidan from Ascophyllum nodosum and Undaria pinnatifida attenuate SARS-CoV-2 infection in vitro and in vivo by suppressing ACE2 and alleviating inflammation - Fang-Shu Shi; Yv-Hao Xie; Yong-Le Yang; Ling-Dong Xu; Jin-Jun Li; Xin Wang; Li-Ying Zhu; Wei-Wei Wang; Pei-li Shen; Yao-Wei Huang; Xiao-Qiong Li (Carbohydrate Polymers, 2024)

Allophane improves anaerobic digestion of chicken manure by alleviating ammonia inhibition and intensifying direct interspecies electron transfer - Yukun Liu; Lanxing Ying; Hui Li; Mukesh Kumar Awasthi; Dong Tian; Jinsong He; Jianmei Zou; Yongjia Lei; Fei Shen (Bioresource Technology, 2024)

AMO modulation of interdecadal background of persistent heavy rainfall in summer over the Huaihe River Basin - Jingwen Yu; Qingquan Li; Yihui Ding; Zhiping Wen; Zhiqiang Gong; Xiaoting Sun; Xinyong Shen; Lili Dong (Climate Dynamics, 2024)
This study used observed rainfall, ERA5 reanalysis, and CMIP6 model datasets to investigate the interdecadal variation and underlying mechanism of persistent heavy rainfall (PHR) over the Huaihe River Basin (HRB) in China during July–August, and to examine the role of the Atlantic Multidecadal Oscillation (AMO) in modulating such rainfall. The results indicate that PHR over the HRB exhibited a marked interdecadal variation. The interdecadal increase in PHR was found attributable primarily to interdecadal enhancement of ascending motion, which might have been due to external forcing by the AMO. The AMO can trigger upper-tropospheric mid–high-latitude Rossby wave trains that can lead to an upper-tropospheric anticyclone and a lower-tropospheric cyclone configuration over the HRB. Increased warm advection and greater transport of water vapor from lower latitudes, caused by enhanced southerlies in the middle–lower troposphere over the HRB, can also lead to enhanced ascending motion over the HRB. Meanwhile, an anomalous cyclone over northeastern China triggered by AMO can transport cold air from higher latitudes to the HRB, boosting convection and promoting the development and duration of PHR. By affecting sea surface temperature in the western North Pacific Ocean, the AMO can also indirectly cause a meridional teleconnection pattern in the lower troposphere, which increases the transport of water vapor to the HRB. Numerical model experiments can reproduce both the interdecadal variations in PHR and the mechanisms of the influence of the AMO on PHR, providing a reliable foundation for understanding and forecasting PHR over the HRB.

Influences of tobacco straw return with lime on microbial community structure of tobacco-planting soil and tobacco leaf quality - Chaoqiang Jiang; Chaolong Zu; Muhammad Riaz; Chen Li; Qifa Zhu; Hao Xia; Qing Dong; Jia Shen (Environmental Science and Pollution Research, 2024)

Spatiotemporal patterns and driving factors of gross primary productivity over the Mongolian Plateau steppe in the past 20 years - Lei Ding; Zhenwang Li; Xu Wang; Beibei Shen; Liujun Xiao; Gang Dong; Lu Yu; Banzragch Nandintsetseg; Zhou Shi; Jinfeng Chang; Changliang Shao (Science of The Total Environment, 2024)

Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Comparative analysis of peak-summer heatwaves in the Yangtze–Huaihe River Basin of China in 2022 and 2013: Thermal effects of the Tibetan Plateau - Geman Lu; Qingquan Li; Xiaoting Sun; Mengchu Zhao; Lili Dong; Qingyuan Wu; Lijuan Wang; Liang Zhao; Chunfeng Duan; Yizhou Yin; Pengling Wang; Xinyong Shen (Atmospheric Research, 2024)

Auto-parametric resonance of a continuous-beam-bridge model under two-point periodic excitation: an experimental investigation and stability analysis - Yuchun Li; Chao Shen; Wei Liu; Dong Li (Earthquake Engineering and Engineering Vibration, 2024)

How does adsorptive fractionation of dissolved black carbon on ferrihydrite affect its copper binding behaviors? A molecular-scale investigation - Mei Huang; Qi Yang; Jianmei Zou; Li Zhao; Jinsong He; Dong Tian; Yongjia Lei; Fei Shen (Water Research, 2024)

Integrated assessment of the pollution and risk of heavy metals in soils near chemical industry parks along the middle Yangtze River - Dong Xu; Zejun Wang; Xiaoyu Tan; Haohan Xu; Dongbo Zhu; Ruili Shen; Kang Ding; Hongcheng Li; Luojing Xiang; Zhibing Yang (Science of The Total Environment, 2024)

Boosting the CO2 electrolysis performance using high entropy stable La0.2Pr0.2Sm0.2Sr0.2Ca0.2Fe0.9Ni0.1O3-δ electrode for symmetric solid oxide electrolysis cells - Zhengpeng Chen; Jiajia Wang; Mingfei Li; Jiangbo Dong; Renci Xu; Jinsong Cheng; Kai Xiong; Mumin Rao; Chuangting Chen; Chenjin Shen; Xiaowei Li; Yihan Ling (Fuel, 2024)

Evaluation of 3-dibutylamino-propylamine aqueous solution for CO2 capture: Promoting the energy-saving regeneration through self-extraction regulation - Zhangfeng Dong; Lijie Que; Wenjun Li; Qiuyao Ren; Chen Wang; Shixuan Li; Bihong Lv; Guohua Jing; Huazhen Shen (Chemical Engineering Journal, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Pyrolysis temperature matters: Biochar-derived dissolved organic matter modulates aging behavior and biotoxicity of microplastics - Honghong Lyu; Hui Zhang; Jinrui Dong; Boxiong Shen; Zi Cheng; Junhui Yu; Ruiyan Li; Ningning Shao; Jingchun Tang (Water Research, 2024)

Enhancing soil carbon and nitrogen through grassland conversion from degraded croplands in China: Assessing magnitudes and identifying key drivers of phosphorus reduction - Yuan Li; Ying Li; Qingping Zhang; Gang Xu; Guopeng Liang; Dong-Gill Kim; Carmen Rosa Carmona; Mei Yang; Jianming Xue; Yangzhou Xiang; Bin Yao; Yuying Shen (Soil and Tillage Research, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Efficient electro-demulsification of O/W emulsions and simultaneous oil removal enabled by a multiscale porous biocarbon electrode - Kui Wang; Hailiang Zhao; Yingming Zhang; Xu Li; Mengyi Xu; Meirong Song; Guangxin Ru; Xiaolei Jiang; Xiuhong Zhu; Dandan Han; Yutao Dong; Kexin Shen; et al. (Chemical Engineering Journal, 2024)

Tumor microenvironment-responsive multifunctional nanoplatform with selective toxicity for MRI-guided photothermal/photodynamic/nitric oxide combined cancer therapy - Shihao Zhou; Chengguang Wu; Pengfei Shen; Liming Zhou; Wenbo Wang; Kai Lv; Chengxiu Wei; Guowei Li; Dong Ma; Wei Xue (Chemical Engineering Journal, 2024)

Structured low-rank representation learning for hyperspectral sparse unmixing - Jian Zhang; Hongsong Dong; Wenlian Gao; Li Zhang; Zhiwen Xue; Xiangfei Shen (International Journal of Remote Sensing, 2024)

Physiological factors contribute to increased competitiveness of grass relative to sedge, forb and legume species under different N application levels - Hao Shen; Shikui Dong; Antonio DiTommaso; Anna S. Westbrook; Shuai Li; Hanzhong Zheng; Yangliu Zhi; Hui Zuo; Qiyun Wang; Junxiang Liu (Science of The Total Environment, 2024)

Climatic factors and fertilization rates co-regulate anaerobic methane oxidation driven by multiple electron acceptors in Chinese paddy fields - Wang-ting Yang; Wei-qi Wang; Evgenios Agathokleous; Ya-nan Bai; Shuai Zhang; Chun Wang; Yan-fang Feng; Jia-qi Liu; Yu-ling Yang; Cai-yu Geng; Li-dong Shen (Journal of Cleaner Production, 2024)

Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the Industrial Revolution recorded by high-resolution stalagmites - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

A 20-year shift in China's sewage sludge heavy metals and its feasibility of nutrient recovery in land use - Xin Li; Shi-jie Yuan; Chen Cai; Xiao-wei Li; Hai-bin Wu; Danni Shen; Bin Dong; Zu-xin Xu (Environmental Pollution, 2024)

Efficient Ag+ adsorption of in-vivo thiol-functionalized diatoms and its application for sensitive surface-enhanced Raman scattering - Mengyuan Li; Dong Liu; Dusan Losic; Shun Wang; Qian Tian; Rongda Yu; Haoyu Li; Yuguo Shen; Yin Zhong; Peng Yuan (Chemical Engineering Journal, 2024)

The swelling induced choline alkali-urea (SICAU) process for sustainable crop straw upgrading - Yuehan Jiang; Feiyue Shen; Baiheng Jiang; Yuheng Hu; Jinguang Hu; Mei Huang; Li Zhao; Hejun Wu; Dong Tian; Fei Shen (Chemical Engineering Journal, 2024)

A review of chitosan in gene therapy: Developments and challenges - Liang Dong; Yanan Li; Hailin Cong; Bing Yu; Youqing Shen (Carbohydrate Polymers, 2024)

Extraction of super high-yield lignin-carbohydrate complexes from rice straw without compromising cellulose hydrolysis - Baiheng Jiang; Feiyue Shen; Yuehan Jiang; Mei Huang; Li Zhao; Yongjia Lei; Jinguang Hu; Dong Tian; Fei Shen (Carbohydrate Polymers, 2024)

A novel hybrid simulated annealing algorithm for colored bottleneck traveling salesman problem - Xueshi Dong; Qing Lin; Fanfan Shen; Qingteng Guo; Qingshun Li (Swarm and Evolutionary Computation, 2023)

Urban canopy height ozone distribution in a Chinese inland city: Effects of anthropogenic NO emissions - Yanan Guan; Ying Shen; Tianyuan Wu; Wenkang Su; Dong Li; Shuangying Ni; Tao Zhang; Jing Han; Erhong Duan (Science of The Total Environment, 2023)

Facile fabrication of functionalized wood evaporator through deep eutectic solvent delignification for efficient solar-driven water purification - Feiyue Shen; Jiayi Xu; Jiaxin Yan; Shiyu Wu; Chenjun He; Wenjie Li; Jinguang Hu; Yanzong Zhang; Dong Tian; Fei Shen (Journal of Environmental Chemical Engineering, 2023)

Improvement of protein structural and functional properties of indica-japonica hybrid rice by radio frequency treatment - Yifei Dong; Yan Cui; Xiaoting Xuan; Liang Zhang; Jiafeng Shen; Jiangang Ling; Suhong Li (Innovative Food Science & Emerging Technologies, 2023)

Banana pseudostem-inspired fluidic photothermal structure towards efficient solar steam generation and continuous salt rejecting - Jiakai Li; Rongxin Lv; Guiqiu Li; Wenqi Luo; Jiashui Wang; Meng Xia; Peng Zhao; Yongyao Chen; Senjia Wu; Qi Chen; Yijun Shen; Meng Li; et al. (Desalination, 2023)

Livestock grazing may weaken N deposition effects on soil C:N:P stoichiometry in alpine grassland of the Qinghai-Tibetan Plateau - Hao Shen; Shikui Dong; Shuai Li; Hanzhong Zheng; Qiyun Wang; Junxiang Liu; Jiannan Xiao; Hui Zuo; Ran Zhang; Xiuchun Yang (CATENA, 2023)

The Warm Arctic—Cold Eurasia Pattern and Its Key Region in Winter in CMIP6 Model Simulations - Liang Zhao; Yunwen Liu; Yihui Ding; Qingquan Li; Wei Dong; Xinyong Shen; Wei Cheng; Haoxin Yao; Ziniu Xiao (Advances in Atmospheric Sciences, 2023)

Insights into the underpinning effect of graphene in Cu1Mn10 on enhancing the low-temperature catalytic activity for CO oxidation - Yafang Shen; Jing Sun; Jingwei Li; Yilin Dong; Wenlong Wang; Zhanlong Song; Xiqiang Zhao; Yanpeng Mao (Environmental Research, 2023)

Mass-produced multiscale unclonable plasmonic security labels by a robotic wet-chemical system - Dong Yu; Zong Liu; Chao-Kai Hu; Yao Shen; Zhi-Jiang Li; Xin-Xin Zhang; Ai-Guo Shen (Chemical Engineering Journal, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Deformation Characteristics of Pipelines Due to Adjacent Excavation in Riprap Reclamation Strata - Xiaohua Bao; Chunxun Liu; Lijuan Li; Jun Shen; Jihao Pan; Qijun Dong; Xiangsheng Chen (Journal of Marine Science and Engineering, 2023)
The Shenzhen Ma Wan area has special geotechnical conditions, with more than 50% of the area being reclaimed rock formations. Riprap reclamation strata are particularly susceptible to significant deformation upon stress release. To comprehensively comprehend the reaction of existing pipelines to the excavation of an adjacent deep foundation pit within the riprap reclamation strata, an interaction of the soil–pipeline was conducted by encompassing both scaled model tests and numerical simulations based on a cross-sea channel project. Firstly, scaled model tests were performed on a soil–pipeline interaction caused by excavation. Subsequently, the numerical model was verified by comparing the numerical simulation results with the scaled model test results. Then, the internal force, strain of the pipeline, and soil surface deformation under the conditions of a soil layer with riprap were analyzed, and the results were compared with the case without riprap. Finally, the influence of the support structures was analyzed. The results indicated that the presence of the riprap in strata led to a 19% increase in vertical displacement of the ground surface and a 35% increase in the pipeline bending moment compared with the case without riprap in the same strata. The maximum internal force and strain occurred at an inclined angle of 45° in the pipeline section. Furthermore, it was found that the first lateral support after excavation played a pivotal role in controlling the overall deformation of the foundation pit. The changes in stiffness in the lateral support were more sensitive to the horizontal displacement than the vertical displacement of the pipeline. The results provide valuable insights for the design and safety evaluation of engineering projects in riprap reclamation strata.

Rh-dispersed Cu nanowire catalyst for boosting electrocatalytic hydrogenation of 5-hydroxymethylfurfural - Wenfei Zhang; Yanbin Qi; Yuan Zhao; Wangxin Ge; Lei Dong; Jianhua Shen; Hongliang Jiang; Chunzhong Li (Science Bulletin, 2023)

Novel ship fuel consumption modelling approaches for speed and trim optimisation: Using engine data as auxiliary - Kangli Wang; Defu Zhang; Zhenyu Shen; Wei Zhu; Hongcai Ye; Dong Li (Ocean Engineering, 2023)

A bispecific nanobody with high sensitivity/efficiency for simultaneous determination of carbaryl and its metabolite 1-naphthol in the soil and rice samples - Min-ling Liu; Zi-jian Chen; Xiao-qing Huang; Hong Wang; Jin-li Zhao; Yu-dong Shen; Lin Luo; Xiao-wei Wen; Bruce Hammock; Zhen-lin Xu (Environmental Pollution, 2023)

Highly active Ag/ZnO/ZnAl-LDH heterojunction photocatalysts for NO removal - Hongyi Tang; Xiao'ai Luo; Wenting Li; Yue Pan; Siqi Wang; Hao Ma; Yu Shen; Ruimei Fang; Fan Dong (Chemical Engineering Journal, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

Integrating ATAC-seq and RNA-seq to identify differentially expressed genes with chromatin-accessible changes during photosynthetic establishment in Populus leaves - Sheng-Ying Zhang; Biligen-Gaowa Zhao; Zhuo Shen; Ying-Chang Mei; Guo Li; Feng-Qin Dong; Jiao Zhang; Qing Chao; Bai-Chen Wang (Plant Molecular Biology, 2023)

Aflatoxin B1 affects porcine alveolar macrophage growth through the calcium signaling pathway mediated by the ceRNA regulatory network - Yu Tian; Pei-Yu Dong; Sheng-Lin Liang; Long Li; Shu-Er Zhang; Francesca Gioia Klinger; Wei Shen; You-Yu Yan; Xi-Feng Zhang (Molecular Biology Reports, 2023)

Different responses of alpine plants to natural climate change reduced coexistence through phenological niche overlap - Shikui Dong; Shuai Li; Yudan Xu; Hao Shen; Houjuan Song; Zhaofei Wu; Shengnan Wu; Bingrong Zhou; Fu Li (Science of The Total Environment, 2023)

Legume-specific SnRK1 promotes malate supply to bacteroids for symbiotic nitrogen fixation - Da Guo; Peng Liu; Qianwen Liu; Lihua Zheng; Sikai Liu; Chen Shen; Li Liu; Shasha Fan; Nan Li; Jiangli Dong; Tao Wang (Molecular Plant, 2023)

Efficient purification of a nitrate and chlorate mixture in water via photoredox activated intermediate coupling-decoupling pathway - Weiping Yang; Xin Li; Ruimin Chen; Shujie Shen; Lei Xiao; Jieyuan Li; Fan Dong (Journal of Hazardous Materials, 2023)

Cascade utilization of crop straw through a FeCl3-mediated deep eutectic solvent biorefinery: Lignin-containing cellulose nanofibers flocculant fabrication followed by fertilizer production - Yiyi Chen; Chaojie Yang; Jinguang Hu; Mei Huang; Li Zhao; Jinsong He; Shaobo Zhang; Fei Shen; Dong Tian (Chemical Engineering Journal, 2023)

Human activity and simultaneous high-pressure anomalies influence the long-duration cold events of winter in China - Liang Zhao; Wei Dong; Xinyong Shen; Yihui Ding; Qingquan Li; Yamin Hu; Ziniu Xiao (Climate Dynamics, 2023)

CNN-based automated trace editing method using Hough transform - Yang Shen; Xiao-lin Hu; Tong-dong Wang; Jia-jia Cui; Si-hao Tao; Ao Li; Qiang Lu; De-zhi Zhang; Wei-guo Xiao (Applied Geophysics, 2023)

Nrf2 protects against methamphetamine-induced nephrotoxicity by mitigating oxidative stress and autophagy in mice - Wenjuan Dong; Jia Wan; Hao Yu; Baoyu Shen; Genmeng Yang; Qianyun Nie; Yan Tian; Lixiang Qin; Chunhui Song; Bingzheng Chen; Lihua Li; Shijun Hong (Toxicology Letters, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Measurement of critical properties for the binary mixture of R744 (carbon dioxide) + R1234ze(E) (trans-1,3,3,3-tetrafluoropropene) - Xiaoyu Yao; Jun Shen; HuiFang Kang; Bo Tang; Zhenxing Li; Jian Li; Xueqiang Dong; Maoqiong Gong (International Journal of Refrigeration, 2023)

From 0D to 3D: Controllable synthesis of ammonium vanadate materials for Zn2+ storage with superior rate performance and cycling stability - Gaopeng Li; Yang Su; Shuang Zhou; Jiajie Shen; Dongtao Liu; Shuhui Lv; Jinxian Wang; Wensheng Yu; Xiangting Dong; Xinlu Wang (Chemical Engineering Journal, 2023)

Identification of Immune-Linked Hub Genes and Diagnostic Model Construction in Schizophrenia - Kun Lian; Zonglin Shen; Runxu Yang; Jing Ye; Binli Shang; Lei Dong; Hongfang Li; Jiabing Wu; Yuqi Cheng; Xiufeng Xu (Journal of Molecular Neuroscience, 2023)
Schizophrenia (SCZ) is a prevalent, severe, and persistent mental disorder with an unknown etiology. Growing evidence indicates that immunological dysfunction is vital in the development of SCZ. Our study aims to uncover potential immune-linked hub genes and immune infiltration characteristics of SCZ, as well as to develop a diagnostic model based on immune-linked central genes. GSE38484 and GSE54913 chip expression data for patients with SCZ and healthy controls were retrieved. Weighted gene co-expression network analysis (WGCNA) was performed to identify major module genes and critical immune-linked genes. Functional enrichment analysis was conducted to elucidate the involvement of key genes in the immunological response to SCZ, along with the examination of their protein interactions. Moreover, 202 peripheral blood samples were examined using the single-sample gene set enrichment analysis (ssGSEA) method to detect distinct immune cell types. Hub immune-linked genes in SCZ were identified using the minimal absolute contraction and selection operator analysis. Receptor profiles of central immune-linked genes were analyzed to distinguish the two groups. Finally, the association between immune-linked hub genes and various types of immune cells was assessed. Our findings revealed ten immune cell types and nine key genes involved in SCZ, including effector memory CD4+ T cells, activated CD8+ T cells, mast cells, naive CD8+ T cells, PBMC, type 17 helper cells (Th17), central memory CD8+ T cells, CD56 bright NK cells, memory B cells, and regulatory T cells. Diagnostic models constructed using LASSO regression exhibited an average area under the curve (AUC) of 0.866. Our results indicate immunological dysfunction as a factor in the development of SCZ. ASGR2 , ADRM1 , AHANK , S100A8 , FUCA1 , AKNA , GATA3 , AHCYL2 , and PTRH2 are the key regulatory genes of immune cells, highlighting their potential as novel therapeutic targets for SCZ.

Loss of swallow tail sign on susceptibility-weighted imaging in neurosyphilis mimicking Alzheimer’s disease: a case report - Xiao-Li Cui; Shen Liu; Yi-Ming Zhang; Hong-Dong Zhao; Jian-Quan Shi (Acta Neurologica Belgica, 2023)

Xanthine-derived reactive oxygen species exacerbates adipose tissue disorders in male db/db mice induced by real-ambient PM2.5 exposure - Leijian Chen; Huankai Li; Yi Ru; Yuanyuan Song; Yuting Shen; Lifang Zhao; Gefei Huang; Yi Chen; Zenghua Qi; Ruijin Li; Chuan Dong; Jiacheng Fang; et al. (Science of The Total Environment, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

An online intelligent management method for wastewater treatment supported by coupling data-driven and mechanism models - Jian-Hui Wang; Du-Jiang Zhao; Wan-Shan Liao; Mohamed S. Mahmoud; Zhi-Wei Guo; Hui-Min Li; Xu Gao; Dong Feng; Long-Fei Shi; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2023)

Transcriptome and physiological determination reveal the effects of selenite on the growth and selenium metabolism in mung bean sprouts - Hua Cheng; Lei Li; Jingzhou Dong; Shiyan Wang; Shuai Wu; Shen Rao; Li Li; Shuiyuan Cheng; Linling Li (Food Research International, 2023)

Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2023)

Fully upgrade lignocellulose to three nanomaterials by combinational pretreatment: Refining straw waste to pesticide nanocarrier - Feiyue Shen; Chenjun He; Yuhang Wang; Jinguang Hu; Mei Huang; Li Zhao; Shaobo Zhang; Dong Tian; Fei Shen (Chemical Engineering Journal, 2023)

Interlayer organic matter within hydroxy-interlayered clay minerals enhances soil organic carbon stability under long-term organic fertilization - Dong Liu; Mengyuan Li; Rongda Yu; Haoyu Li; Yuguo Shen; Qian Tian; Hongling Bu; Chuanqin Huang; Wenfeng Tan (Applied Clay Science, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Enhance the stability of oxygen vacancies in SrTiO3 via metallic Ag modification for efficient and durable photocatalytic NO abatement - Hao Ma; Wenjia Yang; Hongyi Tang; Yue Pan; Wenting Li; Ruimei Fang; Yu Shen; Fan Dong (Journal of Hazardous Materials, 2023)

Electrons of d-orbital (Mn) and p-orbital (N) enhance the photocatalytic degradation of antibiotics by biochar while maintaining biocompatibility: A combined chemical and biological analysis - Jinrui Dong; Pin Li; Xiaoyuan Ji; Yong Kang; Xue Yuan; Jingchun Tang; Boxiong Shen; Huajiang Dong; Honghong Lyu (Journal of Hazardous Materials, 2023)

The effect of B-type procyanidin on free radical and metal ion induced β-lactoglobulin glyco-oxidation via mass spectrometry and interaction analysis - Ling Liu; Qi Dong; Youmeng Kong; Yiru Kong; Ziyin Yu; Bin Li; Haixia Yan; Xu Chen; Yixiao Shen (Food Research International, 2023)

Effects of pile fermentation on the physicochemical, functional, and biological properties of tea polysaccharides - Qian Li; Lu Liu; Jiahan Zhang; Mingyu Dong; Lan Wang; David Julian McClements; Yinxin Fu; Lingyu Han; Peiyi Shen; Xiaoqiang Chen (Food Chemistry, 2023)

Possible influence of the interdecadal variation of the extratropical southern Indian Ocean SST on East Asian summer monsoon precipitation - Xiyi Li; Qingquan Li; Yihui Ding; Song Yang; Lili Dong; Jingwen Yu; Xinyong Shen; Qingyuan Wu; Xiaoting Sun (Atmospheric Research, 2023)

Exogenous Methylglyoxal Ameliorates Source Strength and Retrieves Yield Loss Under Drought Stress During Grain Filling in Maize - Yi-Hsuan Lin; Yu-Ka Jin; Zhen-Yuan Chen; Zu-Dong Xiao; Si Shen; Shun-Li Zhou (Journal of Plant Growth Regulation, 2023)

Evolution of brain network dynamics in early Parkinson’s disease with mild cognitive impairment - Chunguang Chu; Zhen Zhang; Jiang Wang; Liufang Wang; Xiao Shen; Lipeng Bai; Zhuo Li; Mengmeng Dong; Chen Liu; Guosheng Yi; Xiaodong Zhu (Cognitive Neurodynamics, 2023)

Shewanella subflava sp. nov., a novel multi-resistant bacterium, isolated from the estuary of the Fenhe River into the Yellow River - Bi Luo; Jing-Yun Su; Ya-Nan Wang; Li Guan; Kai-Shi Dong; Hui-Jing Niu; Shao-Fei Shen; Yi Li (Antonie van Leeuwenhoek, 2023)

The risk factors associated with traumatic subdural effusion for patients with traumatic brain injury who did not undergo decompressive craniectomy - Xiangzhu Shen; Yafei Han; Haichang Li; Yu Dong; Dezhen Yang; Wei Xu; Shan Zhang (Acta Neurologica Belgica, 2023)

Effect of ubiquitin-proteasome system and autophagy-lysosome pathway on intracellular replication of Brucella.suis - Bingmei Dong; Feng Li; Jinliang Wang; Sufang Lv; Lizhong Miao; Guangjun Guo; Zhiqiang Shen (Veterinary Microbiology, 2023)

Anthropogenic impacts on the nitrate pollution in an urban river: Insights from a combination of natural-abundance and paired isotopes - Wenjing Guo; Dong Zhang; Wenshi Zhang; Shen Li; Ke Pan; Hao Jiang; Quanfa Zhang (Journal of Environmental Management, 2023)

Deicing behavior and residue characteristic on cold surface excited by ultrasonic vibration - Leihu Shen; Dong Li; Yuhe Shang; Jiayong Wang (International Journal of Refrigeration, 2023)

Neurocircuitry of Predatory Hunting - Zheng-Dong Zhao; Li Zhang; Xinkuan Xiang; Daesoo Kim; Haohong Li; Peng Cao; Wei L. Shen (Neuroscience Bulletin, 2023)
Predatory hunting is an important type of innate behavior evolutionarily conserved across the animal kingdom. It is typically composed of a set of sequential actions, including prey search, pursuit, attack, and consumption. This behavior is subject to control by the nervous system. Early studies used toads as a model to probe the neuroethology of hunting, which led to the proposal of a sensory-triggered release mechanism for hunting actions. More recent studies have used genetically-trackable zebrafish and rodents and have made breakthrough discoveries in the neuroethology and neurocircuits underlying this behavior. Here, we review the sophisticated neurocircuitry involved in hunting and summarize the detailed mechanism for the circuitry to encode various aspects of hunting neuroethology, including sensory processing, sensorimotor transformation, motivation, and sequential encoding of hunting actions. We also discuss the overlapping brain circuits for hunting and feeding and point out the limitations of current studies. We propose that hunting is an ideal behavioral paradigm in which to study the neuroethology of motivated behaviors, which may shed new light on epidemic disorders, including binge-eating, obesity, and obsessive-compulsive disorders.

Environmental factors induced macrolide resistance genes in composts consisting of erythromycin fermentation residue, cattle manure, and maize straw - Jianjun Ren; Chuanbao Xu; Yunpeng Shen; Chunyu Li; Liping Dong; Taoli Huhe; Junqiang Zhi; Chongqing Wang; Xingmei Jiang; Dongze Niu (Environmental Science and Pollution Research, 2023)

Four new phenolic glycosides from Dobinea delavayi - Xiu-Rong Wu; Li-Juan Lang; Yi Shen; Xiang Dong; Chao-Jiang Xiao; Bei Jiang (Natural Product Research, 2023)

Multiplex strategy electrochemical platform based on self-assembly dual-site DNA tetrahedral scaffold for one-step detection of diazinon and profenofos - Guanjie Wang; Jiashuai Sun; Baoxin Li; Fukai Guan; Jingcheng Huang; Haowei Dong; Jiali Zhang; Jie Han; Zheng Shen; Deyan Xu; Xia Sun; Yemin Guo; et al. (Science of The Total Environment, 2023)

Transcriptome analysis of liver, gill and intestine in rainbow trout (Oncorhynchus mykiss) symptomatically or asymptomatically infected with Vibrio anguillarum - Qian Yang; Xiao-Dong Yang; Meng-Qun Liu; Chu Zeng; Hong-Kui Zhao; Kai-Wen Xiang; Zhi-Shuai Hou; Hai-Shen Wen; Ji-Fang Li (Fish & Shellfish Immunology, 2023)

High bioethanol titer and yield from phosphoric acid plus hydrogen peroxide pretreated paper mulberry wood through optimization of simultaneous saccharification and fermentation - Pleasure Chisom Ajayo; Qing Wang; Mei Huang; Li Zhao; Dong Tian; Jinsong He; Dexin Fang; Jinguang Hu; Fei Shen (Bioresource Technology, 2023)

Brassica seed meal fumigation restores beneficial bacterial communities by enriching taxa with high resistance and resilience - Junwei Peng; Minchong Shen; Ruihuan Chen; Hong Liu; Yang Sun; Qin Liu; Yuanhua Dong; Jiangang Li (Plant and Soil, 2023)

High-efficient removal of ammonium and co-production of protein-rich biomass from ultrahigh-NH4+ industrial wastewater by mixotrophic Galdieria sulphuraria - Baojun Zhu; Yali Zheng; Hao Shen; Dong Wei; Li Ni; Guoyou Wei (Algal Research, 2023)

Use of tyrosinase-inorganic salt hybrid nanoflowers and tyrosinase-MOF hybrid composites for elimination of phenolic pollutants from industrial wastewaters - Chao-Yun Feng; Kang-Hong Wang; Shuangfei Li; Dong-Shen Liu; Zhen Yang (Chemosphere, 2023)

Habitual feeding patterns impact polystyrene microplastic abundance and potential toxicity in edible benthic mollusks - Senyang Wang; Liang Zheng; Mengyan Shen; Longsheng Zhang; Yiting Wu; Guangyu Li; Chuanbo Guo; Cunzhi Hu; Mingming Zhang; Yanming Sui; Xuexing Dong; Linlan Lv (Science of The Total Environment, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Low temperature plasma suppresses proliferation, invasion, migration and survival of SK-BR-3 breast cancer cells - Xiang Li; Tao Sun; XinRu Zhang; Chao Hou; Qiying Shen; Dong Wang; GuoHua Ni (Molecular Biology Reports, 2023)

Synergistic changes of rhizosphere bacterial community and soil properties in greenhouse soils under long-term tomato monoculture - Keke Dang; Lidong Ji; Lindsey C. Slaughter; Jinfeng Hou; Minchong Shen; Jiangang Li; Yuanhua Dong (Applied Soil Ecology, 2023)

Surfactant recovery and efficient separation of PAHs from surfactant solutions by low-cost waste activated sludge and two-stage design optimization - Dong Zhang; Biao Shen; Ming Zhang; Yuchi Zhong; Ting Lü; Jingang Huang; Hongting Zhao; Li Lu (Environmental Science and Pollution Research, 2023)

Achieving phosphorus recovery at pilot-scale anaerobic anoxic/nitrifying-induced crystallization (A2N-IC) process: Performance, assessment, and challenges - Xiang Li; Shuting Shen; Zhiqiang Fu; Yiran Dong; Hongliang Dai; Xiwu Lu (Chemosphere, 2023)

The conserved L1089 in the S2 subunit of avian infectious bronchitis virus determines viral kidney tropism by disrupting virus-cell fusion - Shu-Yun Li; Yu-Xi Shen; Xue-Lian Xiang; Yong-Xin Li; Nian-Ling Li; An-Dong Wang; Min Cui; Xin-Feng Han; Yong Huang; Jing Xia (Veterinary Microbiology, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

Multi-energies assisted and all-weather recovery of crude oil by superhydrophobic melamine sponge - Yihao Guan; Zhining Wang; Mutai Bao; Xiuping Chen; Limei Dong; Yun Shen; Yiming Li (Journal of Hazardous Materials, 2023)

P450-catalyzed polyethylene oligomer degradation: A quantum mechanics/molecular mechanics study - Mingna Zheng; Yanwei Li; Weiliang Dong; Jie Shen; Qingzhu Zhang (Journal of Cleaner Production, 2023)

Role and regulation of anaerobic methane oxidation catalyzed by NC10 bacteria and ANME-2d archaea in various ecosystems - Wang-ting Yang; Li-dong Shen; Ya-nan Bai (Environmental Research, 2023)

Simultaneous interfacial and bulk defect passivation and interface energy band alignment optimization via In(SCN2H4)3Cl3 diffusion doping for inverted perovskite solar cells - Dong Yang; Yujuan Weng; Zhitao Shen; Mengqi Jin; Hu Shen; Qing Du; Jihong Zheng; Fumin Li; Chong Chen (Chemical Engineering Journal, 2023)

Fe3+-enhanced zero valent iron/peroxymonosulfate (ZVI/PMS) process for the transformation of iopamidol during coagulation and reduction of iodinated disinfection by-products - Yuanxiang Mao; Yifei Wu; Xiaoli Lu; Caiping Sun; Chenglin Li; Yuzhe Chen; Lei Jiang; Qiushi Shen; Qian Zhang; Caocong Liu; Jialiang Liang; Huiyu Dong; et al. (Chemical Engineering Journal, 2023)

Correction to: Important revelations of different degrees of COVID‑19 lockdown on improving regional air quality: a case study of Shijiazhuang, China - Yanan Guan; Ying Shen; Xinyue Liu; Xuejiao Liu; Jing Chen; Dong Li; Man Xu; Litao Wang; Erhong Duan; Li’an Hou; Jing Han (Environmental Science and Pollution Research, 2023)

Source appointment at large-scale and ungauged catchment using physically-based model and dynamic export coefficient - Wenzhuo Wang; Lei Chen; Chen Lin; Yong Liu; Xin Dong; Junfeng Xiong; Guowangcheng Liu; Yuhan Zhang; Jiaqi Li; Zhenyao Shen (Journal of Environmental Management, 2023)

Effect of gradual increase of atmospheric CO2 concentration on nitrification potential and communities of ammonia oxidizers in paddy fields - Bing-jie Ren; Li-dong Shen; Xin Liu; Jing-hao Jin; He-chen Huang; Mao-hui Tian; Yu-ling Yang; Wang-ting Yang; Jia-qi Liu; Cai-yu Geng; Hong-sheng Wu; Zheng-hua Hu (Journal of Environmental Management, 2023)

Membranes with ZIF-8 regulated MXene nanosheet stacks for efficient molecular sieving - Jian Li; Lei Li; Xin Li; Liangliang Dong; Zhenyu Wang; Jiangnan Shen; Bart Van der Bruggen (Desalination, 2023)

A new water-soluble lignin incorporation enhanced the barrier performance of liquid mulching film - Dong Tian; Jing Zhang; Jinguang Hu; Mei Huang; Li Zhao; Yongjia Lei; Jianmei Zou; Shaobo Zhang; Fei Shen (Chemical Engineering Journal, 2023)

Zinc supplementation ameliorates sorafenib-induced cognitive impairment through ROS/JNK signaling pathway - Can-Can Zhou; Yu-Qiong He; Yu-Shuang Qiu; Chen-Xu Ni; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2023)

Important revelations of different degrees of COVID-19 lockdown on improving regional air quality: a case study of Shijiazhuang, China - Yanan Guan; Ying Shen; Xinyue Liu; Xuejiao Liu; Jing Chen; Dong Li; Man Xu; Litao Wang; Erhong Duan; Li’an Hou; Jing Han (Environmental Science and Pollution Research, 2022)

Lead Exposure in Developmental Ages Promotes Aβ Accumulation by Disturbing Aβ Transportation in Blood-Cerebrospinal Fluid Barrier/Blood–Brain Barriers and Impairing Aβ Clearance in the Liver - Can-Can Zhou; Xu-Jie Wang; Zi-Chen Li; Wen-Jie Lu; Yun-Ting Zhang; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2022)

Experimental study on the effects of particle grading on lime-treated slurry with vacuum preloading - Hong-lei Sun; Zhen-qi Weng; Xue-yu Geng; Meng-fen Shen; Xiao-dong Pan; Li Shi; Yuan-qiang Cai (Marine Georesources & Geotechnology, 2022)

Effects of Arctic sea ice in autumn on extreme cold events over the Tibetan Plateau in the following winter: possible mechanisms - Miao Bi; Qingquan Li; Song Yang; Dong Guo; Xinyong Shen; Xiaoting Sun (Climate Dynamics, 2022)
Extreme cold events (ECEs) on the Tibetan Plateau (TP) exert serious impacts on agriculture and animal husbandry and are important drivers of ecological and environmental changes. We investigate the temporal and spatial characteristics of the ECEs on the TP and the possible effects of Arctic sea ice. The daily observed minimum air temperature at 73 meteorological stations on the TP during 1980–2018 and the BCC_AGCM3_MR model are used. Our results show that the main mode of winter ECEs over the TP exhibits the same spatial variation and interannual variability across the whole region and is affected by two wave trains originating from the Arctic. The southern wave train is controlled by the sea ice in the Beaufort Sea. It initiates in the Norwegian Sea, and then passes through the North Atlantic Ocean, the Arabian Sea, and the Bay of Bengal along the subtropical westerly jet stream. It enters the TP from the south and brings warm, humid air from the oceans. By contrast, the northern wave train is controlled by the sea ice in the Laptev Sea. It originates from the Barents and Kara seas, passes through Lake Baikal, and enters the TP from the north, bringing dry and cold air. A decrease in the sea ice in the Beaufort Sea causes positive potential height anomalies in the Arctic. This change enhances the pressure gradient between the Artic and the mid-latitudes, leading to westerly winds in the northern TP, which block the intrusion of cold air into the south. By contrast, a decrease in the sea ice in the Laptev Sea causes negative potential height anomalies in the Artic. This change reduces the pressure gradient between the Artic and the mid-latitudes, leading to easterly winds to the north of the TP, which favors the southward intrusion of cold polar air. A continuous decrease in the amount of sea ice in the Beaufort Sea would reduce the frequency of ECEs over the TP and further aggravate TP warming in winter.

Assessment of DDT and its Metabolites Bioaccessibility in Historically Contaminated Soils Using Unfed and Fed in Vitro Methods - Chao Li; Shen Xu; Dong-xing Guan; Xian-xian Chen; Huan He (Bulletin of Environmental Contamination and Toxicology, 2022)

The Combined Effect of Plastic Particles Size and Concentration on Rotifers’ (Brachionus plicatilis) Performance - Yanming Sui; Senyang Wang; Mohamed Mohsen; Longsheng Zhang; Mengyan Shen; Zhiquan Liu; Haidang Nguyen; Shengmao Zhang; Kaixing Li; Linlan Lv; Xuexing Dong (Journal of Ocean University of China, 2022)

Transcriptomic analyses reveal the effect of nitric oxide on the lateral root development and growth of mangrove plant Kandelia obovata - Ming-Yue Wei; Huan Li; You-Hui Zhong; Zhi-Jun Shen; Dong-Na Ma; Chang-Hao Gao; Yi-Ling Liu; Wen-Hua Wang; Jing-Ya Zhang; Yan-Ping You; Hai-Lei Zheng (Plant and Soil, 2022)

Spatio-temporal baseline and spatial coverage of lunar-based SAR repeat-track interferometry in single- and double-antenna configurations - Jinglong Dong; Qiang Shen; Houjun Jiang; Liming Jiang; Dewei Li; Hansheng Wang; Xiaodong Chen; Yingjun Sun; Guobiao Yao (International Journal of Remote Sensing, 2022)

Influence Mechanism of Different Weathering Degrees on Conversion of Coal to Biogas - Xile Liu; Fenghua Zhao; Hongyu Guo; Zhiwei Dong; Yunsong Li; Ye Shen; Xiaokai Xu (Natural Resources Research, 2022)

F-box only protein 9 and its role in cancer - Shujaat Hussain; Jianshu Dong; Xinli Ma; Jian Li; Shen Chen; Agboybor Clement; Hongmin Liu (Molecular Biology Reports, 2022)

Efficiency and safety of eltrombopag for multi-line failed Chinese patients with immune thrombocytopenia: cases with decreased megakaryocyte response well from single-center experience - Qi Liu; Yingying Shen; Yuzhu Li; Huijin Hu; Wenbin Liu; Yuechao Zhao; Huijie Dong; Yiping Shen; Yuhong Zhou; Baodong Ye; Dijiong Wu (Immunologic Research, 2022)

Improvement of water resistance by Fe2O3/TiO2 photoelectrocatalysts for formaldehyde removal: experimental and theoretical investigation - Jing Dong; Qing Li; Wenjie Xia; Bihong Lv; Guohua Jing; Huazhen Shen; Chung-shin Yuan (Environmental Science and Pollution Research, 2022)

GC–MS fingerprints of essential oils from agarwood grown in wild and artificial environments - Cheng-piao Tian; Xing-dong Yao; Jia-hao Lu; Li-qun Shen; Ai-qun Wu (Trees, 2021)

Development and characterization of 37 SNP markers for the largemouth bass (Micropterus salmoides) by using PCR–RFLP method - Zhou Jiang; Jiao Cui; Jiaqi Shao; Chuanju Dong; Jinxing Du; Yubang Shen; Shengjie Li; Meng Zhang; Xuejun Li (Conservation Genetics Resources, 2021)

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer - Li-rong Yan; Han-xi Ding; Shi-xuan Shen; Xiao-dong Lu; Yuan Yuan; Qian Xu (Functional & Integrative Genomics, 2021)

A zonally-oriented teleconnection pattern induced by heating of the western Tibetan Plateau in boreal summer - Qingquan Li; Mengchu Zhao; Song Yang; Xinyong Shen; Lili Dong; Zhaodong Liu (Climate Dynamics, 2021)
The thermal effect of the Tibetan Plateau (TP) on the northern hemisphere climate has long been a hot topic of scientific research. However, the global effects of the TP heat source are still unclear. We investigate the teleconnection patterns coincident with the TP heat source in boreal summer using both observational data and numerical models including a linearized baroclinic model and an atmospheric general circulation model. The western TP shows the most intense variability in atmospheric heating and the most active connection to atmospheric circulations. The surface sensible heating component of the western TP heat source is associated with a high-latitude wave train propagating from North Japan to central North America through the Bering Sea and Canada. The radiative heating component is accompanied by a wavenumber-4 wave train over Eurasia. We focus on the global zonally-oriented pattern that is connected with the latent heat release from the western TP, referred to here as the TP–circumglobal teleconnection (TP-CGT). The TP-CGT pattern is triggered by the western TP latent heating in two parts starting from the TP: an eastward-propagating wave train trapped in the westerly jet stream and a westward Rossby wave response. The TP-CGT accounts for above 18% of the total variance of the circumglobal teleconnection pattern and modulates mid-latitude precipitation by superimposition. The western TP is the key region in which diabatic heating can initiate the two atmospheric responses concurrently, and the heating over northeastern Asia or the Indian Peninsula is unable to induce the circumglobal pattern directly. The unique geographical location and strong tropospheric heating also make the western TP as a “transit area” of transferring the indirect impact of the Indian summer monsoon (ISM) to the TP-CGT. These results enhance our understanding of the relationship between the circumglobal teleconnection and the ISM and is helpful for improving the prediction of the circumglobal teleconnection variability.

Effect of Modified Clay on the Growth Dynamics and Physio—Biochemical Response of Newly Hatched Larvae of the Marine Medaka (Oryzias melastigma) - Peipei Zhang; Xiuxian Song; Yue Zhang; Huihui Shen; Xueyi Dong; Jing Li; Zhiming Yu (Journal of Marine Science and Engineering, 2021)
An outbreak of harmful algal blooms (HABs) often leads to the death of fish and other marine organisms and causes serious losses to human economic activities. Modified clay (MC) technology is an effective way to control HABs. Although the material and preparation process are based on the premise of green and safety, the potential eco-environmental impacts of MC on non-target organisms should still have to receive attention before field applications can occur. Therefore, the effects of one commonly used modified clay, polyaluminum chloride-modified clay (PAC-MC), on the survival, growth, and oxidative stress of the marine medaka (Oryzias melastigma) were studied. The toxicity test results showed that the 96-h median lethal concentration (96-h LC50) of PAC-MC for newly hatched medaka larvae was 5.204 g/L, which was much higher than the concentration used on site (4–10 t/km2). Within the concentration range of PAC-MC used in this experiment (≤2 g/L), the morphology, heart rate, growth, and aluminum content of larvae did not change with the increase in the modified clay concentration. Low concentrations of PAC-MC (≤0.5 g/L) did not significantly affect catalase (CAT) activity, superoxide dismutase (SOD) activity, peroxidase (POD) activity, and the content of malondialdehyde (MDA), but higher concentrations of PAC-MC (such as 2 g/L) caused oxidative damage to the larvae and increased the antioxidant enzyme activity of the larvae. The present study revealed that under an effective dosage for treating harmful algal blooms on site, PAC-MC had no adverse effects on the survival, growth, oxidative stress, and aluminum content of the newly hatched marine medaka, which provides a scientific basis for the field application of modified clay.

Combined Application of Arbuscular Mycorrhizal Fungi and Exogenous Melatonin Alleviates Drought Stress and Improves Plant Growth in Tobacco Seedlings - Ling Liu; Dong Li; Yilin Ma; Hongtao Shen; Shimin Zhao; Yanfang Wang (Journal of Plant Growth Regulation, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Characteristics of soil erosion and sediment size distribution for different land uses in the Chinese Mollisol region - Hai-ou Shen; Jun Feng; Dong-li Wang; Hong-li Li; Yu Wang (Journal of Mountain Science, 2021)

Evaluation of the efficacy and safety of hydroxychloroquine in comparison with chloroquine in moderate and severe patients with COVID-19 - Qiuyu Li; Cheng Cui; Fei Xu; Jianping Zhao; Nan Li; Haichao Li; Tianbing Wang; Hua Zhang; Na Liu; Yudong Wei; Xiaoye Niu; Yan Xu; et al. (Science China Life Sciences, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Pathological matrix stiffness promotes cardiac fibroblast differentiation through the POU2F1 signaling pathway - Mingzhe Li; Jimin Wu; Guomin Hu; Yao Song; Jing Shen; Junzhou Xin; Zijian Li; Wei Liu; Erdan Dong; Ming Xu; Youyi Zhang; Han Xiao (Science China Life Sciences, 2021)

Degradation significantly decreased the ecosystem multifunctionality of three alpine grasslands: evidences from a large-scale survey on the Qinghai-Tibetan Plateau - Yu-dan Xu; Shi-kui Dong; Hao Shen; Jian-nan Xiao; Shuai Li; Xiao-xia Gao; Sheng-nan Wu (Journal of Mountain Science, 2021)

Julichrome derivatives and gliotoxin from a soil derived Streptomyces sp. - Tong Shen; Le-Mei Li; Ze-Yu Xu; Yong-Dong Wang; Wei-Dong Xie (Natural Product Research, 2021)

A DEM fusion method for ascending and descending orbit StereoSAR DEMs in complicated mountain areas considering SAR echo intensity - Guo-lin Cai; Dong Shen; Ao-li Zhang; Hai-hua Yu; Xuan-yu Zhang (Journal of Mountain Science, 2021)

Isolation and characterisation of N-benzyl tadalafil as a novel adulterant in a coffee-based dietary supplement - Pei-Zhi Dong; Xiao-Pu Liu; Lu Zhang; Guo-Hua Shen; Zi-Long Wang; Guo-Wei Yang; Wei Li; Xin-Hua Xiang (Food Additives & Contaminants: Part A, 2020)

A new demethyl abietane diterpenoid from the roots of Tripterygium wilfordii - Peng Li; Shao-Xin Shen; Ling-Xue Liu; Jian-Hua Xu; Xin-Hua Ma; Dong-Mei Shi; Zhi-Qiang Zhang (Natural Product Research, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Targeted observation analysis of the tides and currents in a Coastal Marine Proving Ground - Jiali Zhang; Anmin Zhang; Xuefeng Zhang; Liang Zhang; Dong Li; Zheqi Shen; Chaohui Sun (Ocean Dynamics, 2020)

A variational successive corrections approach for the sea ice concentration analysis - Xuefeng Zhang; Lu Yang; Hongli Fu; Dong Li; Zheqi Shen; Lianxin Zhang; Xuhui Hu (Acta Oceanologica Sinica, 2020)

Terpenoids from the roots of Leontopodium longifolium and their inhibitory activity on NO production in RAW264.7 cells - Tong Shen; Han Qian; Yong-Dong Wang; Hai-Bei Li; Wei-Dong Xie (Natural Product Research, 2020)

TMEM88 modulates the secretion of inflammatory factors by regulating YAP signaling pathway in alcoholic liver disease - Liang-yun Li; Chen-chen Yang; Su-wen Li; Yu-min Liu; Hao-dong Li; Shuang Hu; Hong Zhou; Jin-liang Wang; Hang Shen; Xiao-ming Meng; Jun Li; Tao Xu (Inflammation Research, 2020)

Bone marrow mesenchymal stem cells combine with normothermic machine perfusion to improve rat donor liver quality—the important role of hepatic microcirculation in donation after circulatory death - Liu Yang; Huan Cao; Dong Sun; Bin Hou; Ling Lin; Zhong-Yang Shen; Hong-Li Song (Cell and Tissue Research, 2020)
Donation after circulatory death (DCD) can expand the donor pool effectively. A gap remains in outcome between DCD livers and living donor livers, warranting improved DCD liver quality and urgent resolution. Bone marrow mesenchymal stem cells (BMMSCs) can regulate immunity, participate in the anti-inflammatory response, and secrete cytokines. We investigated the effect of BMMSCs combined with normothermic machine perfusion (NMP) on DCD liver quality, and the role of microcirculation therein. Rat thoracic aortas were clipped to obtain DCD livers, and a rat NMP system was established. The DCD livers were grouped by preservation method: normal, static cold storage (SCS), NMP (P), and BMMSCs plus NMP (BP); storage time was up to 8 h. Liver function in outflow perfusate was detected by biochemical methods; liver tissue histopathology was observed by hematoxylin–eosin staining; hepatocyte ultrastructure was observed by transmission electron microscopy; hepatocyte apoptosis was detected by terminal deoxynucleotidyl transferase dUTP nick end labeling; liver microcirculation–related indicators were detected by immunofluorescence, immunohistochemistry, Western blotting, and enzyme-linked immunosorbent assay. Compared with SCS, P and BP significantly improved liver function and liver histological damage, reduced hepatocyte apoptosis, and repaired hepatocyte mitochondrial damage after 6 h in vitro. BP also significantly inhibited intrahepatic macrophage activation and intercellular adhesion, improved endothelial damage, and significantly improved endothelin 1–nitric oxide balance and microcirculation perfusion. In conclusion, BP can improve DCD liver microcirculation and quality. The mechanism may be the improvement of improve hepatic sinusoidal endothelial injury and microcirculation perfusion by inhibiting macrophage activation and intercellular adhesion.

Association of Polygenic Risk Score with Age at Onset and Cerebrospinal Fluid Biomarkers of Alzheimer’s Disease in a Chinese Cohort - Wei-Wei Li; Zhen Wang; Dong-Yu Fan; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Ling Li; Heng Yang; Yu-Hui Liu; Xian-Le Bu; Wang-Sheng Jin; Fan Zeng; et al. (Neuroscience Bulletin, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Simultaneous calcium recordings of hippocampal CA1 and primary motor cortex M1 and their relations to behavioral activities in freely moving epileptic mice - Xi Dong; Xin Zhang; Feifei Wang; Nannan Liu; Aili Liu; Yuanyuan Li; Liangpeng Wei; Feng Chen; Shiyang Yuan; Kai Zhang; Shaowei Hou; Qingyan Jiao; et al. (Experimental Brain Research, 2020)

Biofertilizer application triggered microbial assembly in microaggregates associated with tomato bacterial wilt suppression - Menghui Dong; Mengli Zhao; Zongzhuan Shen; Xuhui Deng; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Qirong Shen (Biology and Fertility of Soils, 2020)

Multi-hole joint acquisition of a 3D-RVSP in a karst area: Case study in the Wulunshan Coal Field, China - Ming-Shun Hu; Dong-Ming Pan; Fu-Bao Zhou; Juan-Juan Li; Yang-Zhou Wang; Shen-En Chen; Yong-Zhong Xu (Applied Geophysics, 2020)

Acute response of Pacific white shrimp Litopenaeus vannamei to high-salinity reductions in osmosis-, metabolism-, and immune-related enzyme activities - Min Shen; Yanting Cui; Renjie Wang; Tiantian Dong; Haibin Ye; Shusheng Wang; Ranghui Fu; Yuquan Li (Aquaculture International, 2020)

Effectiveness of management zoning designed for flagship species in protecting sympatric species - Xiaoli Shen; Sheng Li; William J. McShea; Dajun Wang; Jianping Yu; Xiaogang Shi; Wei Dong; Xiangcheng Mi; Keping Ma (Conservation Biology, 2020)
Flagship species have been used widely as umbrella species (i.e., species with large home range whose protection often provides protection for sympatric species) in the management of China's nature reserves. This conflation of flagship and umbrella species is best represented by the giant panda ( Ailuropoda melanoleuca ) and other large, endangered mammals designated as conservation targets in site selection and planning of reserves. Few empirical studies have tested the effectiveness of flagship species as surrogates for a broader range of sympatric species. Using extensive camera‐trap data, we examined the effectiveness of management zones designated to protect flagship (target) species in conserving sympatric species in 4 wildlife reserves (Gutianshan, Changqing, Laohegou, and Wolong). We tested whether the progression from peripheral to core zones was associated with an increasing habitat association for both target and sympatric species. The distribution patterns of the study species across the zones in each reserve indicated a disparity between management zones and the species’ habitat requirements. Management zone was included in the final model for all target species, and most of them had higher occurrence in core zones relative to less‐protected zones, but zone was not a predictor for most of the sympatric species. When management zone was associated with the occurrence of sympatric species, threatened species generally had higher detections in core zones, whereas common species had higher detections outside of the core zone. Our results suggested that reserve planning based on flagship species does not adequately protect sympatric species due to their specialized habitat requirements. We recommend re‐examining the effectiveness of management zoning and urge a multispecies and reserve‐wide monitoring plan to improve protection of China's wildlife.

The efflux pump inhibitor tetrandrine exhibits synergism with fluconazole or voriconazole against Candida parapsilosis - Ya-Jing Zhao; Wei-Da Liu; Yong-Nian Shen; Dong-Mei Li; Kun-Ju Zhu; Hong Zhang (Molecular Biology Reports, 2019)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Genetic Association Between NGFR, ADAM17 Gene Polymorphism, and Parkinson’s Disease in the Chinese Han Population - Wei-Wei Li; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Qian-Qian Shi; Jing Mei; Heng Yang; Fa-Ying Zhou; An-Yu Shi; Tao Zhang; Xiu-Qing Yao; Zhi-Qiang Xu; et al. (Neurotoxicity Research, 2019)

Characterization of the complete plastid genome sequence of the endangered species Bretschneidera sinensis - Fengping Dong; Xinhong Liu; Yanqin Zhang; Ruisen Lu; Zhixin Zheng; Xin Shen; Yingang Li (Conservation Genetics Resources, 2019)

A genomic island in a plant beneficial rhizobacterium encodes novel antimicrobial fatty acids and a self‐protection shield to enhance its competition - Dandan Wang; Zhihui Xu; Guishan Zhang; Liming Xia; Xiaoyan Dong; Qing Li; Mark R. Liles; Jiahui Shao; Qirong Shen; Ruifu Zhang (Environmental Microbiology, 2019)
Summary Rhizobacteria devote a relatively large percentage of their genomes to encode bioactive natural products that are important for competition in the rhizosphere. In this study, a plant beneficial rhizobacterium Bacillus velezensis SQR9 was discovered to produce novel antibacterial fatty acids, Bacillunoic acids, which are encoded on a genomic island (GI). This GI contains a hybrid type I fatty acid synthase (FAS)‐polyketide synthase (PKS) system and an ABC transporter. The FAS was predicted to synthesize a primer that was transferred to the PKS to synthesize Bacillunoic acids. The synthesized Bacillunoic acids inhibit the growth of diverse bacteria, with the strongest activity against closely related Bacillus strains, the ABC transporter exported the toxic Bacillunoic acids upon their induction for protecting the producing strain. The inhibition of other Bacillus strains by Bacillunoic acids extended the antimicrobial spectrum of SQR9 and enhanced its competition with closely related root‐associated bacteria. So, through the obtaining of this GI by horizontal gene transfer, strain SQR9 not only acquired a competitive weapon but also acquired a self‐protecting shield, which increased its competition with other rhizobacteria.

Effects of perinatal dioxin exposure on development of children: a 3-year follow-up study of China cohort - Zheng Wang; Jin Guo Hang; Hao Feng; Li Li Shi; Jing Jian Dong; Bin Shen; Ting Luo; Ren Mei Cai; Ling Jie Shen; Teruhiko Kido; Xian Liang Sun (Environmental Science and Pollution Research, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Noncoding rare variants of TBX6 in congenital anomalies of the kidney and urinary tract - Shuangshuang Dong; Chunyan Wang; Xueping Li; Qian Shen; Xiaoyi Fu; Mingyan Wu; Chengcheng Song; Nan Yang; Yanhua Wu; Hongyan Wang; Li Jin; Hong Xu; et al. (Molecular Genetics and Genomics, 2019)

Ochratoxin A causes mitochondrial dysfunction, apoptotic and autophagic cell death and also induces mitochondrial biogenesis in human gastric epithelium cells - Qian Li; Zhen Dong; Weiguang Lian; Jinfeng Cui; Juan Wang; Haitao Shen; Wenjing Liu; Jie Yang; Xianghong Zhang; Hongjuan Cui (Archives of Toxicology, 2019)

Presence of bacteroidales as a predicator of human enteric viruses in Haihe River of Tianjin City, China - Shuqing Zhou; Dong Yang; Qunying Xu; Zhongwei Yang; Min Jin; Jing Yin; Huaran Wang; Kun Zhou; Lianqi Wang; Junwen Li; Zhiqiang Shen (Environmental Science and Pollution Research, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Potassium Influences Expression of Key Genes Involved in Sorbitol Metabolism and Its Assimilation in Pear Leaf and Fruit - Changwei Shen; Yan Li; Jie Wang; Yosef Al Shoffe; Caixia Dong; Qirong Shen; Yangchun Xu (Journal of Plant Growth Regulation, 2018)

Short-term effects of ambient air pollutants and myocardial infarction in Changzhou, China - Yongquan Yu; Shen Yao; Huibin Dong; Minghui Ji; Zhiyong Chen; Guiying Li; Xingjuan Yao; Shou-Lin Wang; Zhan Zhang (Environmental Science and Pollution Research, 2018)

Lower Fractional Anisotropy in the Gray Matter of Amygdala-Hippocampus-Nucleus Accumbens Circuit in Methamphetamine Users: an In Vivo Diffusion Tensor Imaging Study - Yadi Li; Wenhua Zhou; Haibo Dong; Wenwen Shen; Jianbing Zhang; Feng Li; Lingjun Zhang (Neurotoxicity Research, 2018)

Melatonin Augments the Effects of Fluoxetine on Depression-Like Behavior and Hippocampal BDNF–TrkB Signaling - Kun Li; Si Shen; Yu-Tian Ji; Xu-Yun Li; Li-San Zhang; Xiao-Dong Wang (Neuroscience Bulletin, 2018)

Successful Treatment by Surgery of a Primary Cutaneous Mucormycosis Caused by Mucor irregularis - Guan-zhao Liang; Wen-qi Xu; Xiao-li Zheng; Huan Mei; Gui-xia Lv; Yong-nian Shen; Dong-mei Li; Wei-da Liu (Mycopathologia, 2018)

The complete mitochondrial genome sequence of Changbai Mountains wild boar (Cetartiodactyla: Suidae) - Zhen-Dong Tan; Lin-Yuan Shen; Xiao Cheng; Mai-Lin Gan; Shun-Hua Zhang; Li Zhu (Conservation Genetics Resources, 2018)

Impact of previous episodes of hepatic encephalopathy on short-term brain function recovery after liver transplantation: a functional connectivity strength study - Yue Cheng; Gaoyan Zhang; Wen Shen; Li-Xiang Huang; Li Zhang; Shuang-Shuang Xie; Xiao-Dong Zhang; Baolin Liu (Metabolic Brain Disease, 2018)

Inhibitory effects of Dioscin on atherosclerosis and foam cell formation in hyperlipidemia rats - Ping Wang; Li-ya He; Guo-dong Shen; Rui-lin Li; Jun-li Yang (Inflammopharmacology, 2017)

Nicotiana benthamiana NbbZIP28, a possible regulator of unfolded protein response, plays a negative role in viral infection - Lili Shen; Fangfang Li; Wenfeng Dong; Wei Liu; Yumei Qian; Jinguang Yang; Fenglong Wang; Yuanhua Wu (European Journal of Plant Pathology, 2017)

Identification and sex expression profiling of odorant-binding protein genes in Trichogramma japonicum (Hymenoptera: Trichogrammatidae) using RNA-Seq - Jia-Dong Wu; Zhao-Can Shen; Hai-Qing Hua; Fan Zhang; Yuan-Xi Li (Applied Entomology and Zoology, 2017)

Construction of the First High-Density Genetic Linkage Map and Analysis of Quantitative Trait Loci for Growth-Related Traits in Sinonovacula constricta - Donghong Niu; Yunchao Du; Ze Wang; Shumei Xie; Haideng Nguyen; Zhiguo Dong; Heding Shen; Jiale Li (Marine Biotechnology, 2017)

Laboratory assessment of bioleaching of shallow eutrophic sediment by immobilized photosynthetic bacteria - Shiyong Sun; Shenglan Fan; Kexuan Shen; Shen Lin; Xiaoqin Nie; Mingxue Liu; Faqin Dong; Jian Li (Environmental Science and Pollution Research, 2017)

Aquatic animals promote antibiotic resistance gene dissemination in water via conjugation: Role of different regions within the zebra fish intestinal tract, and impact on fish intestinal microbiota - Jialun Fu; Dong Yang; Min Jin; Weili Liu; Xin Zhao; Chenyu Li; Tianyu Zhao; Jingfeng Wang; Zhixian Gao; Zhiqiang Shen; Zhigang Qiu; Jun‐Wen Li (Molecular Ecology, 2017)
The aqueous environment is one of many reservoirs of antibiotic resistance genes ( ARG s). Fish, as important aquatic animals which possess ideal intestinal niches for bacteria to grow and multiply, may ingest antibiotic resistance bacteria from aqueous environment. The fish gut would be a suitable environment for conjugal gene transfer including those encoding antibiotic resistance. However, little is known in relation to the impact of ingested ARG s or antibiotic resistance bacteria ( ARB ) on gut microbiota. Here, we applied the cultivation method, qPCR , nuclear molecular genetic marker and 16S rDNA amplicon sequencing technologies to develop a plasmid‐mediated ARG transfer model of zebrafish. Furthermore, we aimed to investigate the dissemination of ARG s in microbial communities of zebrafish guts after donors carrying self‐transferring plasmids that encode ARG s were introduced in aquaria. On average, 15% of faecal bacteria obtained ARG s through RP 4‐mediated conjugal transfer. The hindgut was the most important intestinal region supporting ARG dissemination, with concentrations of donor and transconjugant cells almost 25 times higher than those of other intestinal segments. Furthermore, in the hindgut where conjugal transfer occurred most actively, there was remarkable upregulation of the mRNA expression of the RP 4 plasmid regulatory genes, trbBp and trfAp . Exogenous bacteria seem to alter bacterial communities by increasing Escherichia and Bacteroides species, while decreasing Aeromonas compared with control groups. We identified the composition of transconjugants and abundance of both cultivable and uncultivable bacteria (the latter accounted for 90.4%–97.2% of total transconjugants). Our study suggests that aquatic animal guts contribute to the spread of ARG s in water environments.

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)

Antimicrobial activity and membrane interaction mechanism of the antimicrobial peptides derived from Rana chensinensis with short sequences - Min Shen; Weibing Dong; Jun Qian; Li Zou (Biologia, 2017)

Efficacy and safety of escitalopram in treatment of severe depression in Chinese population - Tianmei Si; Gang Wang; Fude Yang; Yiru Fang; Maosheng Fang; Jijun Li; Jicheng Dong; Xinhua Shen; Jianmin Zhuo; Qing Rui; Jinan Wang; Hu Cuili (Metabolic Brain Disease, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Assessment of HCV genotypes in Yunnan Province of Southwest China - Qiongfen Li; Yufeng Yao; Yunsong Shen; Danfeng Cao; Yalin Li; Shuqiong Zhang; Wei Cun; Mingbo Sun; Jiankun Yu; Li Shi; Shaozhong Dong (Virus Genes, 2017)

Control of the pollution of antibiotic resistance genes in soils by quorum sensing inhibition - Bai-Min Lai; Kun Zhang; Dong-Sheng Shen; Mei-Zhen Wang; Jia-Li Shentu; Na Li (Environmental Science and Pollution Research, 2017)

Potential role of anammox in nitrogen removal in a freshwater reservoir, Jiulonghu Reservoir (China) - Li-dong Shen; Hai-xiang Cheng; Xu Liu; Jian-hui Li; Yan Liu (Environmental Science and Pollution Research, 2017)

NLRP3 inflammasome: a promising target in ischemic stroke - Li Gao; Qing Dong; Zhenghong Song; Fei Shen; Jianquan Shi; Yansheng Li (Inflammation Research, 2017)

Dimethyl Fumarate and Monomethyl Fumarate Promote Post-Ischemic Recovery in Mice - Yang Yao; Weimin Miao; Zhijia Liu; Wei Han; Kaibin Shi; Yi Shen; Handong Li; Qiang Liu; Ying Fu; DeRen Huang; Fu-Dong Shi (Translational Stroke Research, 2016)

Short communication: antiviral activity of porcine IFN-λ3 against porcine epidemic diarrhea virus in vitro - Haiyan Shen; Chunhong Zhang; Pengju Guo; Zhicheng Liu; Minhua Sun; Junying Sun; Linlin Li; Jiawen Dong; Jianfeng Zhang (Virus Genes, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Expression quantitative trait loci in long non-coding RNA PAX8-AS1 are associated with decreased risk of cervical cancer - Jing Han; Wen Zhou; Meiqun Jia; Juan Wen; Jie Jiang; Jufang Shi; Kai Zhang; Hongxia Ma; Jibin Liu; Jiansong Ren; Min Dai; Zhibin Hu; et al. (Molecular Genetics and Genomics, 2016)

Analysis of gene expression and histone modification between C4 and non-C4 homologous genes of PPDK and PCK in maize - Xiu-mei Dong; Yuan Li; Qing Chao; Jie Shen; Xiu-jie Gong; Biligen-gaowa Zhao; Bai-chen Wang (Photosynthesis Research, 2016)

Toll-Like Receptor 4 Deficiency Causes Reduced Exploratory Behavior in Mice Under Approach-Avoidance Conflict - Chunlu Li; Yixiu Yan; Jingjing Cheng; Gang Xiao; Jueqing Gu; Luqi Zhang; Siyu Yuan; Junlu Wang; Yi Shen; Yu-Dong Zhou (Neuroscience Bulletin, 2016)

New Re-Os isotopic constrains on the formation of the metalliferous deposits of the Lower Cambrian Niutitang formation - Yong Fu; Lin Dong; Chao Li; Wenjun Qu; Haoxiang Pei; Wenlang Qiao; Bing Shen (Journal of Earth Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Nitrogen loss through anaerobic ammonium oxidation in agricultural drainage ditches - Li-dong Shen; Pei-hui Zheng; Shi-jie Ma (Biology and Fertility of Soils, 2016)

Evidence for anaerobic ammonium oxidation process in freshwater sediments of aquaculture ponds - Li-dong Shen; Hong-sheng Wu; Zhi-qiu Gao; Yun-jie Ruan; Xiang-hua Xu; Ji Li; Shi-jie Ma; Pei-hui Zheng (Environmental Science and Pollution Research, 2016)

Provenance of detrital zircons in the Late Triassic Sichuan foreland basin: constraints on the evolution of the Qinling Orogen and Longmen Shan thrust-fold belt in central China - Yong Zhang; Dong Jia; Li Shen; Hongwei Yin; Zhuxin Chen; Haibin Li; Zhigang Li; Chuang Sun (International Geology Review, 2015)

Promoter analysis and RNA interference of CYP6ab4 in the silkworm Bombyx mori - Guo-Dong Zhao; Yi-Ling Zhang; Yun-Lei Liu; Bing Li; Yu-Hua Chen; Ya-Xiang Xu; Qing-You Xia; Wei-De Shen; Zheng-Guo Wei (Molecular Genetics and Genomics, 2015)

Effect from low-level exposure of oxytetracycline on abundance of tetracycline resistance genes in arable soils - Jia-li Shentu; Kun Zhang; Dong-sheng Shen; Mei-zhen Wang; Hua-jun Feng (Environmental Science and Pollution Research, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Erratum to: Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2015)

Nitrite-Dependent Anaerobic Methane-Oxidising Bacteria: Unique Microorganisms with Special Properties - Li-dong Shen; Zhan-fei He; Hong-sheng Wu; Zhi-qiu Gao (Current Microbiology, 2015)

Sulfide oxidation and nitrate reduction for potential mitigation of H2S in landfills - Yuan Fang; Yao Du; Huan Feng; Li-Fang Hu; Dong-Sheng Shen; Yu-Yang Long (Biodegradation, 2015)

Nanoparticulate TiO2 Protection of Midgut Damage in the Silkworm (Bombyx mori) Following Phoxim Exposure - Ling Wang; Mingyu Su; Xiaoyang Zhao; Jie Hong; Xiaohong Yu; Bingqing Xu; Lei Sheng; Dong Liu; Weide Shen; Bing Li; Fashui Hong (Archives of Environmental Contamination and Toxicology, 2015)

Bioaccessibility and health risk of heavy metals in ash from the incineration of different e-waste residues - Xiao-Qing Tao; Dong-Sheng Shen; Jia-Li Shentu; Yu-Yang Long; Yi-Jian Feng; Chen-Chao Shen (Environmental Science and Pollution Research, 2015)

Effects of added polyacrylamide on changes in water states during the composting of kitchen waste - Yu-Qiang Yang; Zhuo-Xian Chen; Xue-Qing Zhang; Li-Fang Hu; Dong-Sheng Shen; Yu-Yang Long (Environmental Science and Pollution Research, 2015)

High-Level S100A6 Promotes Metastasis and Predicts the Outcome of T1–T2 Stage in Clear Cell Renal Cell Carcinoma - Xiangjun Lyu; Hongzhao Li; Xin Ma; Xintao Li; Yu Gao; Dong Ni; Donglai Shen; Liangyou Gu; Baojun Wang; Yu Zhang; Xu Zhang (Cell Biochemistry and Biophysics, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Myocardial infarction worsens glomerular injury and microalbuminuria in rats with pre-existing renal impairment accompanied by the activation of ER stress and inflammation - Zhifeng Dong; Penglong Wu; Yongguang Li; Yuan shen; Ping Xin; Shuai Li; Zhihua Wang; Xiaoyan Dai; Wei Zhu; Meng Wei (Molecular Biology Reports, 2014)

The expression profile and promoter analysis of β-N-acetylglucosaminidases in the silkworm Bombyx mori - Yuan-fen Zhai; Ming-xia Huang; Yu Wu; Guo-dong Zhao; Jie Du; Bing Li; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Decreased Astroglial Monocarboxylate Transporter 4 Expression in Temporal Lobe Epilepsy - Bei Liu; Le Niu; Ming-Zhi Shen; Lei Gao; Chao Wang; Jie Li; Li-Jia Song; Ye Tao; Qiang Meng; Qian-Li Yang; Guo-Dong Gao; Hua Zhang (Molecular Neurobiology, 2014)

Monitoring of urban heat island in Shanghai, China, from 1981 to 2010 with satellite data - Cheng-fan Li; Di Shen; Jiang-shan Dong; Jing-yuan Yin; Jun-juan Zhao; Dan Xue (Arabian Journal of Geosciences, 2014)

An object-oriented daytime land fog detection approach based on NDFI and fractal dimension using EOS/MODIS data - Xiongfei Wen; Dunmei Hu; Xinyi Dong; Fan Yu; Debao Tan; Zhe Li; Yitong Liang; Daxiang Xiang; Shaohong Shen; Chengfang Hu; Bo Cao (International Journal of Remote Sensing, 2014)

Anterolateral minithoracotomy versus median sternotomy for mitral valve disease: a meta-analysis - Chao Ding; Da-ming Jiang; Kai-yu Tao; Qun-jun Duan; Jie Li; Min-jian Kong; Zhong-hua Shen; Ai-qiang Dong (Journal of Zhejiang University-SCIENCE B, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

BIG1, a Brefeldin A-Inhibited Guanine Nucleotide-Exchange Factor, Is Required for GABA-Gated Cl– Influx Through Regulation of GABAA Receptor Trafficking - Cuixian Li; Shaorui Chen; Yang Yu; Chun Zhou; Ying Wang; Kang Le; Dong Li; Weiwei Shao; Liang Lu; Yan You; Jin Peng; Heqing Huang; et al. (Molecular Neurobiology, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Expression analysis and RNA interference of BmCarE-10 gene from Bombyx mori - Guo-dong Zhao; Ming-xia Huang; Yi-ling Zhang; Xue-cen Wang; Jie Du; Bing Li; Yu-hua Chen; Ya-xiang Xu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Asiatic Acid Inhibits Adipogenic Differentiation of Bone Marrow Stromal Cells - Zheng-Wei Li; Cheng-dong Piao; Hong-Hui Sun; Xian-Sheng Ren; Yun-Shen Bai (Cell Biochemistry and Biophysics, 2014)

Evaluation of snow depth and snow cover fraction simulated by two versions of the flexible global ocean-atmosphere-land system model - Kun Xia; Bin Wang; Lijuan Li; Si Shen; Wenyu Huang; Shiming Xu; Li Dong; Li Liu (Advances in Atmospheric Sciences, 2014)

Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2014)

Variability of atlantic meridional overturning circulation in FGOALS-g2 - Wenyu Huang; Bin Wang; Lijuan Li; Li Dong; Pengfei Lin; Yongqiang Yu; Tianjun Zhou; Li Liu; Shiming Xu; Kun Xia; Ye Pu; Lu Wang; et al. (Advances in Atmospheric Sciences, 2014)

Full-length sequence analysis of hepatitis E virus isolates: showing potential determinants of virus genotype and identity - Dong Yang; Mei Jiang; Min Jin; Zhigang Qiu; Weihong Cui; Zhiqiang Shen; Bo Li; Lianfeng Gong; Zhaoli Chen; Xinwei Wang; Jun-Wen Li (Virus Genes, 2013)

Genetic structure of rice black-streaked dwarf virus populations in China - Xiao Yin; Fang-Qiang Zheng; Wei Tang; Qin-Qin Zhu; Xiang-Dong Li; Guang-Min Zhang; Huan-Ting Liu; Bao-Shen Liu (Archives of Virology, 2013)

Association between CYP1A1 polymorphisms and esophageal cancer: a meta-analysis - Fang-Fang Shen; Fu-You Zhou; Qi-Si Xue; Ying Pan; Lu Zheng; Hua Zhang; Li-Dong Wang; Hou-Feng Zheng (Molecular Biology Reports, 2013)

First report on the allelopathic effect of Tychonema bourrellyi (Cyanobacteria) against Microcystis aeruginosa (Cyanobacteria) - Jihai Shao; Liang Peng; Si Luo; Gongliang Yu; Ji-dong Gu; Shen Lin; Renhui Li (Journal of Applied Phycology, 2013)

Cryptotanshinone inhibits human glioma cell proliferation by suppressing STAT3 signaling - Liang Lu; Cuixian Li; Dong Li; Ying Wang; Chun Zhou; Weiwei Shao; Jin Peng; Yan You; Xinwen Zhang; Xiaoyan Shen (Molecular and Cellular Biochemistry, 2013)

Retrograde cPLA2α/Arachidonic Acid/2-AG Signaling Is Essential for Cerebellar Depolarization-Induced Suppression of Excitation and Long-Term Potentiation - Li-Da Su; De-Juan Wang; Dong Yang; Ying Shen; Ying-Hong Hu (The Cerebellum, 2013)

Colloidal diatomite, radionickel, and humic substance interaction: a combined batch, XPS, and EXAFS investigation - Guodong Sheng; Runpu Shen; Huaping Dong; Yimin Li (Environmental Science and Pollution Research, 2013)

Simulation of sea ice in FGOALS-g2: Climatology and late 20th century changes - Shiming Xu; Mirong Song; Jiping Liu; Bin Wang; Lijuan Li; Wenyu Huang; Li Liu; Kun Xia; Wei Xue; Ye Pu; Li Dong; Si Shen; et al. (Advances in Atmospheric Sciences, 2013)

Preliminary evaluations of FGOALS-g2 for decadal predictions - Bin Wang; Mimi Liu; Yongqiang Yu; Lijuan Li; Pengfei Lin; Li Dong; Li Liu; Jiping Liu; Wenyu Huang; Shiming Xu; Si Shen; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

Evaluation of grid-point atmospheric model of IAP LASG version 2 (GAMIL2) - Lijuan Li; Bin Wang; Li Dong; Li Liu; Si Shen; Ning Hu; Wenqi Sun; Yong Wang; Wenyu Huang; Xiangjun Shi; Ye Pu; Guangwen Yang (Advances in Atmospheric Sciences, 2013)

The flexible global ocean-atmosphere-land system model, Grid-point Version 2: FGOALS-g2 - Lijuan Li; Pengfei Lin; Yongqiang Yu; Bin Wang; Tianjun Zhou; Li Liu; Jiping Liu; Qing Bao; Shiming Xu; Wenyu Huang; Kun Xia; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

Co-digestion of kitchen waste and fruit–vegetable waste by two-phase anaerobic digestion - Yu-Qiang Yang; Dong-Sheng Shen; Na Li; Dong Xu; Yu-Yang Long; Xuan-Yu Lu (Environmental Science and Pollution Research, 2013)

Molecular cloning and expression of 17β-hydroxysteroid dehydrogenase type 2 gene in Hu sheep - Chang Long Wang; Shi Jia Ying; Zi Yu Wang; Hui Jun Xing; Li Zhong Wang; Dong Yang He; Shen Hua Xiao; Feng Wang (Molecular Biology Reports, 2013)

Analyzing the promoters of two CYP9A genes in the silkworm Bombyx mori by dual-luciferase reporter assay - Si-Si Zhao; Guo-Dong Zhao; Tian-Yuan Di; Hua Ding; Xiao-Ling Wan; Bing Li; Yu-Hua Chen; Ya-Xiang Xu; Wei-De Shen; Zheng-Guo Wei (Molecular Biology Reports, 2013)

Expression pattern of L-FABP gene in different tissues and its regulation of fat metabolism-related genes in duck - Jun He; Yong Tian; Jinjun Li; Junda Shen; Zhengrong Tao; Yan Fu; Dong Niu; Lizhi Lu (Molecular Biology Reports, 2013)

Transesterification of Rapeseed Oil to Biodiesel on CaO/α-Fe Hollow Fiber Catalyst: Optimization by Response Surface Methodology - Lin Lin; Xiaoqiang Li; Fengjie Cui; Haining Zhou; Xiangqian Shen; Mingdong Dong (BioEnergy Research, 2012)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Association of STAT4 rs7574865 polymorphism with autoimmune diseases: a meta-analysis - Ya-ling Liang; Hua Wu; Xi Shen; Pei-qiang Li; Xiao-qing Yang; Li Liang; Wei-hua Tian; Li-feng Zhang; Xiao-dong Xie (Molecular Biology Reports, 2012)

Association of the CYP1B1 Leu432Val polymorphism with the risk of prostate cancer: a meta-analysis - Lingling Cui; Kelsey Dillehay; Weimin Chen; Deliang Shen; Zhongyun Dong; Wenjie Li (Molecular Biology Reports, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

A novel SNP of liver-type fatty acid-binding protein gene in duck and its associations with the intramuscular fat - Jun He; Jiucheng Chen; Lizhi Lu; Yong Tian; Zhengrong Tao; Deqian Wang; Jinjun Li; Guoqin Li; Junda Shen; Yan Fu; Dong Niu (Molecular Biology Reports, 2012)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Isolation and Identification of a Pathogen of Silkworm Bombyx mori - Heng-Ping Tao; Zhong-Yuan Shen; Feng Zhu; Xiao-Fang Xu; Xu-Dong Tang; Li Xu (Current Microbiology, 2011)

Large-scale analysis of phosphorylated proteins in maize leaf - Ying-Dong Bi; Hong-Xia Wang; Tian-Cong Lu; Xiao-hui Li; Zhuo Shen; Yi-Bo Chen; Bai-Chen Wang (Planta, 2011)

Variabilities of Two Drechslerella dactyloides Isolates in Korea and High Predacity Against Bursaphelenchus xylophilus - Zhen Wang; Chun-Yan Wang; Li-Juan Gu; Bai-Shen Sun; Dong-Liang Zhang; Lei Liu; Mi-Ra Lee; Chun-Ling Wang; Zheng Li; Eun-Kyung Mo; Chang-Keun Sung (Current Microbiology, 2011)

Evaluation of cleaner production audit in pharmaceutical production industry: case study of the pharmaceutical plant in Dalian, P. R. China - Li Zhi-dong; Zhang Shu-shen; Zhang Yun; Zhang Yong; Wei Li (Clean Technologies and Environmental Policy, 2011)

Bio-immobilization of Cu and Zn in recirculated bioreactor landfill - Yu-Yang Long; Li-Fang Hu; Jing Wang; Cheng-Ran Fang; Ruo He; Dong-Sheng Shen (Environmental Science and Pollution Research, 2010)

A New Hazardous Solid Waste Detoxication Method: Semi-solid Fenton Process (SSFP) - Li-Fang Hu; Yu-Yang Long; Hua-Jun Feng; Jun Yao; Cheng-Ran Fang; Dong-Sheng Shen (Water, Air, & Soil Pollution, 2010)

Cloning and characterization of a functional flavanone-3ß-hydroxylase gene from Medicago truncatula - Xiaoye Shen; Stefan Martens; Mingliang Chen; Daofeng Li; Jiangli Dong; Tao Wang (Molecular Biology Reports, 2010)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Sequence and Phylogenetic Analysis of SSU rRNA Gene of Five Microsporidia - ShiNan Dong; ZhongYuan Shen; Li Xu; Feng Zhu (Current Microbiology, 2010)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

High-pressure eclogite-blueschist metamorphic belt and closure of paleo-Tethys Ocean in Central Qiangtang, Qinghai-Tibet plateau - Cai Li; Qingguo Zhai; Yongsheng Dong; Shen Liu; Chaoming Xie; Yanwang Wu (Journal of Earth Science, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

High beta diversity of bacteria in the shallow terrestrial subsurface - Jianjun Wang; Yucheng Wu; Hongchen Jiang; Chunhai Li; Hailiang Dong; Qinglong Wu; Janne Soininen; Ji Shen (Environmental Microbiology, 2008)
Summary While there have been a vast number of studies on bacterial alpha diversity in the shallow terrestrial subsurface, beta diversity – how the bacterial community composition changes with spatial distance – has received surprisingly limited attention. Here, bacterial beta diversity and its controlling factors are investigated by denaturing gradient gel electrophoresis and cloning of samples from a 700‐cm‐long sediment core, the lower half of which consisted of marine‐originated sediments. According to canonical correspondence analysis with variation partitioning, contemporary environmental variables explain beta diversity in a greater proportion than depth. However, we also found that community similarity decayed significantly with spatial distance and the slopes of the distance–decay relationships are relatively high. The high beta diversity indicates that the bacterial distribution patterns are not only controlled by contemporary environments, but also related to historical events, that is, dispersal or depositional history. This is highlighted by the different beta diversity patterns among studied sediment layers. We thus conclude that the high beta diversity in the shallow terrestrial subsurface is a trade‐off between historical events and environmental heterogeneity. Furthermore, we suggest that the high beta diversity of bacteria is likely to be recapitulated in other terrestrial sites because of the great frequency of high geochemical and/or historical variations along depth.

Root Exudates Increase Metal Accumulation in Mixed Cultures: Implications for Naturally Enhanced Phytoextraction - Chun Ling Luo; Zhen Guo Shen; Xiang Dong Li (Water, Air, & Soil Pollution, 2008)

Depressive-like behavior in mice recently recovered from motor disorders after 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Sha Ma; Wei Zhou; Zheng Wei; Yu-Xiang Zheng; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2008)

Improving ovary and embryo culture techniques for efficient resynthesis of Brassica napus from reciprocal crosses between yellow-seeded diploids B. rapa and B. oleracea - Jing wen; Jin-xing Tu; Zai-yun Li; Ting-dong Fu; Chao-zhi Ma; Jin-xiong Shen (Euphytica, 2008)

Hot NTA Application Enhanced Metal Phytoextraction from Contaminated Soil - Chun-Ling Luo; Zhen-Guo Shen; Xiang-Dong Li (Water, Air, & Soil Pollution, 2008)

FtsY Affects Sporulation and Antibiotic Production by whiH in Streptomyces coelicolor - Xue-Ling Shen; Hui-Jun Dong; Xiao-Ping Hou; Wen-Jun Guan; Yong-Quan Li (Current Microbiology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genetic and epigenetic instabilities induced by tissue culture in wild barley (Hordeum brevisubulatum (Trin.) Link) - Xiaoling Li; Xiaoming Yu; Ningning Wang; Qizhi Feng; Zhenying Dong; Lixia Liu; Jinglin Shen; Bao Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Study on Metsulfuron-Methyl Degradation in Simulated Wheat (Triticum Asetivum L.) Rhizospheric Soil with Penicillium sp. Inoculation - Yong Hua He; Dong Sheng Shen; Li Fang Hu; Yin Mei Zhu (Water, Air, & Soil Pollution, 2007)

Genetic diversity within Oryza rufipogon germplasms preserved in Chinese field gene banks of wild rice as revealed by microsatellite markers - Li-Zhi Gao; Chi-Hong Zhang; Dao-Yuan Li; Da-Jian Pan; Ji-Zeng Jia; Yu-Shen Dong (Biodiversity and Conservation, 2006)

A novel strategy using biodegradable EDDS for the chemically enhanced phytoextraction of soils contaminated with heavy metals - Chun-Ling Luo; Zhen-Guo Shen; Alan J. M. Baker; Xiang-Dong Li (Plant and Soil, 2006)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Strategy for the Improvement of Prodigiosin Production by a Serratia marcescens Mutant through Fed-Batch Fermentation - Jin-li Tao; Xue-dong Wang; Ya-ling Shen; Dong-zhi Wei (World Journal of Microbiology and Biotechnology, 2005)

High-level production of soluble tumor necrosis factor-related apoptosis-inducing ligand (Apo2L/TRAIL) in high-density cultivation of recombinant Escherichia coli using a combined feeding strategy - Ya-Ling Shen; Yue Zhang; Ai-You Sun; Xiao-Xia Xia; Dong-Zhi Wei; Sheng-Li Yang (Biotechnology Letters, 2004)

An improved chromosome preparation from male gametophyte of Laminaria japonica (Heterokontophyta) - Li Ran Zhou; Ji Xun Dai; Song Dong Shen (Hydrobiologia, 2004)

Refolding and purification of Apo2L/TRAIL produced as inclusion bodies in high-cell-density cultures of recombinant Escherichia coli - Ya-Ling Shen; Xiao-Xia Xia; Yue Zhang; Jian-Wen Liu; Dong-Zhi Wei; Sheng-Li Yang (Biotechnology Letters, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)